We Still Demand! Redefining Resistance in Sex and Gender Struggles - Adamyk, Natalie (Labour / Le Travail, 2018)
The article reviews the book, "We Still Demand! Redefining Resistance in Sex and Gender Struggles," edited by Patrizia Gentile, Gary Kinsman, and L. Pauline Rankin.

England's Great Transformation: Law, Labour, and the Industrial Revolution - Frank, Christopher (Labour / Le Travail, 2018)
The article reviews the book, "England's Great Transformation: Law, Labour, and the Industrial Revolution," by Marc Steinberg.

Be Wise! Be Healthy! Morality and Citizenship in Canadian Public Health Campaigns - Kealey, Linda (Labour / Le Travail, 2018)
The article reviews the book, "Be Wise! Be Healthy! Morality and Citizenship in Canadian Public Health Campaigns," by Catherine Carstairs, Bethany Philpott, and Sara Wilmshurst.

The Great Cowboy Strike: Bullets, Ballots, and Class Conflicts in the American West - Laegreid, Renee M. (Labour / Le Travail, 2018)
The article reviews the book, "The Great Cowboy Strike: Bullets, Ballots, and Class Conflicts in the American West," by Mark Lause.

Immigrant Girl, Radical Woman: A Memoir from the Early Twentieth Century - Mayer, Heather (Labour / Le Travail, 2018)
The article reviews the book, "Immigrant Girl, Radical Woman: A Memoir from the Early Twentieth Century," by Matilda Rabinowitz.

Masterless Men: Poor Whites and Slavery in the Antebellum South - Rothman, Joshua D. (Labour / Le Travail, 2018)
The article reviews the book, "Masterless Men: Poor Whites and Slavery in the Antebellum South," by Keri Leigh Merritt.

For Class and Country: The Patriotic Left and the First World War - Weier, Jonathan (Labour / Le Travail, 2018)
The article reviews the book, "For Class and Country: The Patriotic Left and the First World War," by David Smith.

Will the Ontario Labour Movement Return to Class Struggle as Austerity Deepens? - Gindin, Sam (Canadian Dimension, 2018)
The Ontario labour movement is in deep crisis, and has been staggering since the end of the 1990s. Given the labour movement’s historic role in leading and supporting progressive change, its current disorientation should be a matter of alarm to its members of course, but also to anyone concerned with countering the insatiable greed and social destructiveness of capitalism. --Introduction

Preferences for the Distribution of Incomes in Modern Societies: The Enduring Influence of Social Class and Economic Context - Andersen, Robert; Yaish, Meir (Canadian Public Policy, 2018)
Using International Social Survey Program data, we explore the relationship between economic context and attitudes with respect to the distribution of incomes in 20 modern societies, including Canada. Our findings demonstrate that economic inequality has an enduring influence on attitudes. Consistent with the economic self-interest thesis, preferences for equality are strongest among those in working-class occu- pations. Moreover, independent of one’s own social class, one’s father’s social class has a similar enduring impact on attitudes later in life. These relationships are relatively similar across the 20 societies we explore. Still, significant differences in attitudes can be explained by national economic context. We find a strong positive relationship between national-level inequality and opinions on how much inequality there ought to be in the income distribution. In contrast to previous research, however, our findings suggest that national-level economic prosperity and equality of opportunity have little influence on public opinion.

Community Unionism Without the Community? Lessons from Labor-Community Coalitions in the Canadian Child Care Sector - Black, Simon (Labor Studies Journal, 2018)
The theory and practice of community unionism has been central to discussions of alt-labor, union renewal, and revitalization, particularly in relation to union praxis at the urban or local scale. This comparative case study explores two labor-community campaigns to defend public child care services in the context of neoliberal austerity in urban/suburban space. While labor-community coalitions are a necessary—if not sufficient—condition for success, in urban/suburban contexts in which community allies are weak and municipal administrations hostile, public-sector unions must continue to play a leading role in campaigns despite the risk of being cast as defenders of sectional interests rather than of the public good. In such contexts, union involvement in community organizing is a necessary precursor to successful labor-community campaigns.

Individual Financial Returns from Quebec Pension Plan Reform Options: Analyzing Proposals to Renew a Second-Pillar Retirement Income Program - Boisclair, David; Lacroix, Guy; Marchand, Steeve; Michaud, Pierre-Carl (Canadian Public Policy, 2018)
We use simulation methods and a detailed tax calculator to analyze the likely effects of two recent pro- posals aimed at reforming the Quebec Pension Plan (QPP): the federal proposal, eventually implemented throughout Canada, and the Quebec government’s December 2016 proposal. Accounting for education- adjusted life expectancy, earnings variability over the course of a career, and their interactions with the tax code and retirement income system, we find that internal rates of return (IRRs) for new QPP contribu- tions are similar under both reforms for individuals with lifetime average annual earnings of more than $40,000. Both reforms yield substantial IRRs for low-income individuals. Although the Quebec proposal offers higher IRRs for individuals earning less than $40,000, the federal proposal yields greater present value benefits for these same individuals. We show that if new QPP benefits were exempted from the Guaranteed Income Supplement (GIS) clawback, and provided that the working income tax benefit and GIS were not enhanced, the two reforms would yield similar IRRs for individuals with average earnings of more than $15,000. The QPP reform would thus better focus on the middle-income earners originally targeted by reform advocates.

How Do Older Laid-Off Workers Get By: Reemployment, Early Retirement, or Social Insurance Benefits? - Finnie, Ross; Gray, David (Canadian Public Policy, 2018)
We investigate the post-layoff configuration of income sources and pathways of prime-age and older laid- off workers exhibiting a high degree of prior attachment. Using a unique Canadian administrative database that links the event of the involuntary layoff with detailed data on income receipt, we track all of their sources of income over an interval spanning five years after layoff. We conduct a multivariate statistical analysis of the incidence of relying on income from several alternative sources, specifically early retirement (both public and private), reemployment, self-employment, or reliance on social insurance benefits (other than pensions). The two most common states for laid-off workers who have not yet reached normal retirement age are early retirement and continued labour market activity. Our findings indicate that the older workers are at the point of layoff, the greater the likelihood is that they will rely on pension income as their primary income source. This incidence of reliance on pension income also increases with the number of years elapsed since the point of layoff.

Health and Capacity to Work of Older Canadians: Gender and Regional Dimensions - Milligan, Kevin; Schirle, Tammy (Canadian Public Policy, 2018)
We address health capacity to work among older Canadian workers with a specific focus on differences by gender and region. We find that in 2012 men would have needed to work more than five additional years between ages 55 and 69 to keep pace with how much men worked in 1976, holding health capacity constant. For working women, the comparable result is only two years more work. Most of these gaps arose before the mid-1990s; since then, employment advances have offset mortality improvements. Regionally, more than half the Ontario–Atlantic employment difference among older men is rooted in health differences.

Do Large Employers Treat Racial Minorities More Fairly? An Analysis of Canadian Field Experiment Data - Banerjee, Rupa; Reitz, Jeffrey G.; Oreopoulos, Phil (Canadian Public Policy, 2018)
Analysis of amended data from a large-scale Canadian employment audit study (Oreopoulos 2011) shows substantial organization size differences in discrimination against skilled applicants with Asian (Chinese, Indian, or Pakistani) names in the decision to call for an interview. In organizations with more than 500 employees, Asian-named applicants are 20 percent less likely to receive a callback; in smaller organizations, the disadvantage is nearly 40 percent. Large organizations may discriminate less frequently because of more resources in recruitment and training, more human resources development, and greater experience with diversity. Anonymized résumé review may allow organizations to test hiring procedures for discrimination fairly inexpensively.

Lived Experiences of Social Unionism: Toronto Homecare Workers in the late 2000s - Cranford, Cynthia; Hick, Angela; Birdsell Bauer, Louise (Labor Studies Journal, 2018)
This article examines workers’ experiences with a union characterized by a social unionist framing and repertoire in the political realm and bureaucratic servicing of problems in the workplace realm. It analyzes interviews with members and officials about union strategies within privatized homecare predominately provided by immigrant women in Toronto. Workers report both consensual and tense relations with clients prompting them to praise their union’s political strategies yet criticize its limited workplace support. Findings indicate the importance of framing and repertoire that connect quality work with quality care, yet indicate a complex labor process that requires more conceptual and strategic attention.

Abstracts / Résumés, Fall / Automne 2018 (Labour / Le Travail, 2018)
English/French abstracts of articles in the Fall 2018 issue.

Firms as Political Entities – Saving Democracy through Economic Bicameralism - Adams, Roy J. (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "Firms as Political Entities -- Saving Democracy through Economic Bicameralism," by Isabelle Ferreras.
Keywords: Bicameralism; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Democracy; Economics; Industrial democracy; Labor Unions; Saving

La dynamique de construction d’une GRH sociétale dans une PME française du secteur de l’économie sociale et solidaire - Adla, Ludivine; Gallego-Roquelaure, Virginie (Relations industrielles / Industrial Relations, 2018)
Dans notre monde globalisé, l’aire de jeux des acteurs n’est plus circonscrite à la structure, mais elle est, désormais, élargie au territoire. Cet effacement des frontières organisationnelles tend à favoriser le développement d’une logique partenariale, y compris en matière de gestion des ressources humaines (GRH) au regard des bouleversements de l’environnement socio-économique. C’est dans ce contexte actuel qu’une nouvelle forme émergente de GRH apparaît, se situant dans une démarche de RSE (responsabilité sociétale des entreprises) étendue qui ne se restreint plus uniquement à certains aspects sociaux. L’objectif de cet article est d’étudier une approche alternative de la GRH qui se veut plus sociétale. Nous nous attachons à répondre à la problématique suivante : comment instaurer une GRH sociétale en PME ? Utilisant l’approche contextualiste de Pichault et Nizet (2013), nous soulignons l’importance pour le dirigeant de mobiliser des acteurs tant internes qu’externes pour atteindre cet objectif. À partir du cas d’une PME française du secteur de l’économie solidaire, nous explorons, grâce à des récits de vie, des entretiens semi-directifs, des observations participantes et non participantes, ainsi que des analyses documentaires, le processus de construction de cette nouvelle forme de GRH. Nos résultats mettent en lumière trois étapes-clés : 1- l’émergence de cette GRH autour de la création d’un pacte social; 2- son évolution source d’adhésion et de frustration; et, enfin, 3-la diffusion de cette GRH alternative auprès des partenaires externes.

Inside the Mobilities Regime of Newfoundland and Labrador’s Construction Megaprojects: Experiences of Rotational Work Close to Home - Barber, Lachlan (Labour / Le Travail, 2018)
This article explores the experiences of construction-industry workers commuting to major project sites with a view to broadening understandings of the meaning and impact of the development of extractive industries in Newfoundland and Labrador since the 1990s. Theoretically, the article draws upon and develops the concept of “mobilities regimes,” a formulation that locates relations of power and inequality in the co-constitution of mobility and institutional structures. The empirical findings are based on research conducted between December 2014 and June 2016 as part of the On the Move Partnership, a research initiative examining employment-related geographical mobility (e-rgm) in a variety of sectors and provinces across Canada. The focus is on mobility associated with projects that fall under the provincial Special Project Order (spo) legislation. A total of 60 interviews to date have been conducted with workers as well as with key informants, including government officials, employers, and labour organizations. The central argument is that a mobilities regime is discernible not only in policies and project documents produced by governments, employers, and labour organizations, but also in the experiences of workers. These gendered experiences reveal that Newfoundland and Labrador’s spo projects enable people who may otherwise commute interprovincially to work close to home, but this work has contradictory meanings for the men and women involved due to the mobility it entails. By making visible the experiences of workers in the mobilities regimes of much-celebrated projects, the article encourages reflection on the effects on workers and their families of the underlying capitalist imperatives driving Newfoundland and Labrador’s contemporary economic transition.

Syndicalisme et santé au travail - Baril-Gingras, Geneviève (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Syndicalisme et santé au travail," edited by Lucie Goussard et Guillaume Tiffon.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Framing, Resources and Repertoire of Local Trade Union Action for Health and Safety: A Study Conducted with a Quebec Central Labour Body - Baril-Gingras, Geneviève; Dubois-Ouellet, Sarah (Relations industrielles / Industrial Relations, 2018)
Employment and working conditions having an impact on health and safety are some of the most important concerns of workers. Amongst the various means by which trade unions contribute to prevention, the contribution of Worker Safety Representatives (WSR) is well-established and the most studied, including their participation in joint occupational health and safety committees (JOHSC). However, there are surprisingly few studies examining the place of OHS as an issue of workers’ collective action. Conducted with a large Quebec Central Labour Body, this study aims to understand why and how local-level unions concentrate upon these issues, the repertoire of means that they employ and the context that supports or hindus such actions. The conceptual framework is based on previous realistic evaluations of OHS preventive interventions and includes Levesque and Murray’s (2010) trade union power resources and strategic capabilities. In phase I, eleven semi-structured interviews were conducted with union staff members and elected representatives from different sectors, covering a wide array of activities such as unionization, training, negotiation, OHS prevention and compensation. Results also refer to five case studies (phase 2) of local-level trade unions identified by phase 1 respondents as particularly active in relation to prevention. The process by which working conditions having a negative impact on OHS are framed (or not) as trade union issues is examined. Levers and barriers are also identified. Factors affecting the presence of resources for trade union autonomous action aimed at prevention (like the integration of WSR to the union core structure, release time for prevention, etc.) are highlighted. A widely diverse repertoire of workplace-level trade union means of action for OHS is also highlighted by the interviews and case studies, not limited just to those provided by the Quebec OHS regime. It includes the recourse to labour relations mechanisms (e.g. negotiation and strike) and is based on an autonomous agenda, including mobilization. The potential of OHS issues for union revitalization is discussed, as well as the barriers that must be overcome.

Going the Extra Mile: Managers and Supervisors as Moral Agents for Workers with Disability at Two Social Enterprises - Bartram, Timothy; Cavanagh, Jillian; Sim, Stephen; Pariona-Cabrera, Patricia; Meacham, Hannah (Relations industrielles / Industrial Relations, 2018)
This study examines the ethical management of workers with disability (WWD) employed at two social enterprises in Australia. Viewed largely through the spectrum of institutionally-based conflict in the employment relationship, this research draws on a framework of situated moral agency (Wilcox, 2012) to establish the ways in which WWD are afforded opportunities to engage in work and how managers and supervisors practise situated moral agency at the workplace. A qualitative case study approach is used with 62 participants through semi-structured interviews and focus groups. Key findings demonstrate supervisors constantly have to reshape and reinterpret human resource management (HRM) policies and practices to exercise and extend moral agency. This phenomenon suggests contradictions between moral agency and ethical management practice within current HRM regimes. The key message of the paper is that HRM does not always support the ethical management of WWD. Consequently, we question the ethical nature of contemporary HRM policy and practice for WWD, and argue for further research to unpack ethical ways to more effectively support WWD in the workplace. For WWD to be included at work, achieve life skills and their goals, managers and supervisors need to engage with their moral agency. Finally, we draw implications for management and employment relations theory and practice.
Keywords: action morale; disability; discapacidad; discernimiento moral; empresas sociales; entreprises sociales; ethical management; gestion des ressources humaines; gestion éthique; gestión de recursos humanos; gestión ética; handicap; human resource management; moral agency; social enterprises

Users / Patients as Industrial Relations Actors: A Structurationist Analysis - Bellemare, Guy; Briand, Louise; Havard, Christelle; Naschberger, Christine (Relations Industrielles / Industrial Relations, 2018)
This paper proposes a structurationist model that revises the notion of actors in industrial relations (Bellemare, 2000), reconsiders the frontiers of the industrial relations system (Bellemare and Briand 2006, Legault and Bellemare, 2008) and encompasses the developments of "life politics." This model is illustrated by the influence of users/patients on the work organization and governance bodies of a University Hospital in France, as well as on the health care system (public policies, research priorities, etc.).
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Corporate governance; Governance; Health care services policy; Hospitals; Influence; Labor Unions; Labor relations; Patients; Public health; Studies; Work organization

La culpabilité au travail : La parole aux salariés - Berthe, Bénédicte; Chédotal, Camille (Relations industrielles / Industrial Relations, 2018)
La culpabilité est une émotion couramment éprouvée dans la vie quotidienne. L’objectif de cette recherche était de l’étudier dans le cadre du travail. Une recherche exploratoire a donc été menée afin, d’une part, d’identifier les situations générant de la culpabilité au travail ainsi que les effets de cette émotion et, d’autre part, de déterminer si la culpabilisation est une stratégie de management permettant d’obtenir davantage de travail de la part des salariés. Les personnes interviewées sont des salariés aux profils variés selon l’âge, le sexe, le poste occupé, le secteur d’activité, la taille de l’entreprise et le statut. Vingt-huit entretiens semi-directifs ont ainsi été menés. Les résultats identifient les caractéristiques de la culpabilité éprouvée au travail en révélant que cette dernière est familière, d’intensité et de fréquence variables, et évolutive. L’analyse des entretiens révèle aussi huit situations génératrices de culpabilité qui sont liées aux phénomènes suivants : une absence ou un retard, la perception d’un travail globalement mal fait, des demandes ou des promesses non suivies, des comportements ou attitudes non corrects, des caractéristiques personnelles (par exemple, un manque de compétence), un client ou un collègue qui souffrent et ne peuvent être aidés, un manque de temps ainsi que l’impact du travail sur la vie privée. Cette recherche montre que la culpabilité ressentie génère une gêne chez les personnes. Mais elle a, surtout, des effets positifs sur le travail réalisé par les salariés. La culpabilité a généralement un effet bénéfique sur les efforts au travail, sauf quand cette émotion est trop intense. La culpabilisation est un autre axe important de cette étude. Si elle est bien constatée par les répondants, il en ressort qu’elle est jugée inefficace lorsqu’elle émane des supérieurs. Elle est alors rejetée et mal vécue. Cet article ouvre des perspectives de recherche afin, d’une part, d’approfondir la place et le rôle de cette émotion et, d’autre part, de développer des implications managériales en termes de bien-être au travail et de performance au travail.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Work-Related Deaths in Canada - Bittle, Steven; Chen, Ashley; Hébert, Jasmine (Labour / Le Travail, 2018)
This paper critically examines official statistics on workplace fatalities in Canada. Each year the Association of Workers’ Compensation Boards of Canada reports on the number of workers who die from a work-related injury or illness/disease. The problem, however, is that these data report the number of deaths that were accepted for compensation; it is not a system for tracking all work-related deaths. Drawing from a range of data sources and employing a broad definition of what constitutes death at work we attempt to generate a more accurate estimate of the number of work-related fatalities in Canada. In so doing our goal is not to produce a definitive number of annual deaths at work – an impossibility given the paucity of data sources – but instead to challenge dominant ways of conceptualizing what constitutes a work-related fatality and thus contribute to ongoing efforts to raise academic, political, and public awareness about this important issue. In this sense our goal is to question whether official statistics regarding workplace fatalities are complete when set against a broader understanding of what constitutes death at work.

La désindustrialisation : une fatalité ? - Blanchet, Yves (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "La désindustrialisation : une fatalité ?," edited by Jean-Claude Daumas, Ivan Kharaba and Philippe Mioche.

Austérité, flexibilité et précarité au Québec : la fuite en avant - Boucher, Marie-Pierre; Noiseux, Yanick (Labour / Le Travail, 2018)
L’évolution de l’emploi au Québec et au Canada est marquée par la multiplication des statuts d’emploi, la précarisation et la résurgence du phénomène des travailleurs et travailleuses pauvres. Après un rapide rappel des transformations marquant un glissement vers des politiques néolibérales survenues à la fin des années 1970, nous examinons les récentes transformations de la politique sociale liée au travail à l’ère de l’austérité. Pour ce qui est du gouvernement fédéral, nous examinons le programme d’assurance-emploi ainsi que les programmes concernant les travailleurs migrants temporaires. Pour ce qui est du gouvernement du Québec, nous nous attardons surtout sur les politiques d’aide sociale, ainsi que sur les services de garde à l’enfance. Nous traitons ces programmes en tant que politiques d’emploi et mettons en relief le rôle joué par l’État dans l’approfondissement du virage néolibéral amorcé il y a maintenant près de quarante ans.

La qualité d’emploi en France : cartographie et classification des professions d’exécution - Brolis, Olivier; Devetter, François-Xavier (Relations industrielles / Industrial Relations, 2018)
Cet article vise, en s’appuyant sur L’Enquête Conditions de travail (2013), à construire une typologie des professions relevant d’un statut « ouvrier » ou « employé » à partir du niveau et du type de qualité de l’emploi qu’elles induisent. Cette approche de la qualité d’emploi par les professions apparaît importante pour trois raisons complémentaires : d’abord, parce que la nature de la profession s’avère déterminante au-delà des caractéristiques des individus qui l’occupent pour expliquer les écarts en termes de qualité de l’emploi; ensuite, du fait de l’importance de la nature des professions dans la détermination des règles encadrant le travail; et, enfin, en raison du rôle joué par les politiques publiques dans le soutien de la qualité dans certaines professions.
Keywords: France; Francia; calidad de empleo; clasificación; classification; job quality; low-skilled occupations; profesiones poco calificadas; professions peu qualifiées; qualité de l’emploi

How Can the Organizing Work Involved in the Joint Regulation of Lean Projects Promote an Enabling Organization and Occupational Health? - Bruère, Sébastien; Bellemare, Marie; Caroly, Sandrine (Relations industrielles / Industrial Relations, 2018)
The objective of this article is, through an empirical study, to further understanding of the actions and decisions taken in the context of Lean implementation projects carried out under joint regulation (Lévesque and Murray, 1998) agreements. We, therefore, attempt to identify factors that may facilitate the organizing work involved in joint regulation of Lean projects to allow workers to develop a broader range of health-minded work methods and habits. Our assumption is that factors which influence joint regulation, such as the union’s capacity for action, management’s attitude and the purpose of the change, also influence the occupational health outcomes of Lean projects. We believe that the organizing work involved in joint regulation (actions and decisions) has an impact on these factors and influences the occupational health outcomes. Our research question is therefore this: What are the actions and decisions involved in joint regulation of Lean implementation projects that lead to closer correspondence with enabling organization criteria? This empirical study was exploratory in nature and had a multiple case study design. Two cases of lean projects were documented through eight individual interviews and the collection of documents. The main results indicate that, while joint regulation appears essential in terms of meeting enabling organization criteria, it alone is insufficient to explain the health effects of Lean projects. All stakeholders need to define the project goals, modes of assessment and management rules, both cooperatively and transparently, and through their involvement in decisions regarding all processes.

The Fight for $15: The Right Wage for a Working America - Bush, Dave (Labour / Le Travail, 2018)
The article reviews the book, "The Fight for $15: The Right Wage for a Working America," by David Rolf.

Just Work? Migrant Workers' Struggles Today - Calnitsky, Naomi Alisa (Labour / Le Travail, 2018)
This article reviews the book, "Just Work? Migrant Workers' Struggles Today," edited by Aziz Choudry and Mondli Hlatshwayo.

Labours of Love: Family, Human Rights, and Worker Invisibility in Seasonal Mexican Farm Worker Agricultural Migrations to Canada, 1974–Present - Calnitsky, Naomi Alisa (Left History: An Interdisciplinary Journal of Historical Inquiry and Debate, 2018)
This article provides a focused review of the history of seasonal and “foreign” farm labour migration in Canada, and in particular the Canadian Seasonal Agricultural Workers Program (SAWP). It underscores how Mexican migrant workers in particular have been portrayed in Canadian narrative discourses, drawn primarily from political and journalistic sources in Canada in the postwar period.  Extended to Mexico in 1974, the SAWP has a longer history of managed agricultural migration in Canada that is also introduced. The article discusses leitmotifs linked to the history of temporary migration between Mexico and Canada: the fundamental place of family and gender relations; the trope of the male migrant as “breadwinner” (despite the later emergence of women migrants in the program); Mexican officials based in Canada and their role in mitigating labour disputes and unionization efforts among the seasonal migrant class in Canada; and the subjective, “subaltern” stories of migrant workers uncovered through an oral history case study carried out in British Columbia and Manitoba from 2012–2015. It introduces other thematic problems including exclusion/invisibility, human rights, patterns of remuneration, and “complementarity” in farm work, in a context of prior reliance upon the managed internal migration of First Nations’ harvest workers in both Ontario’s and Manitoba’s agricultural sectors.

Tax, Order, and Good Government: A New Political History of Canada, 1867–1917 - Campbell, J. Peter (Labour / Le Travail, 2018)
This article reviews the book, "Tax, Order, and Good Government: A New Political History of Canada, 1867–1917," by E.A. Heaman.

Griffintown: Identity and Memory in an Irish Diaspora Neighbourhood - Caron, Matthieu (Labour / Le Travail, 2018)
The article reviews the book, "Griffintown: Identity and Memory in an Irish Diaspora Neighbourhood," by Matthew Barlow.

Migration and Agriculture. Mobility and change in the Mediterranean Area - Castracani, Lucio (Labour / Le Travail, 2018)
This article reviews the book, "Migration and Agriculture. Mobility and change in the Mediterranean Area" by Alessandra Corrado, Carlos de Castro et Domenico Perrotta.

Blood, Sweat, and Fear: Violence at Work in the North American Auto Industry, 1960–80 - Clark, Daniel (Labour / Le Travail, 2018)
This article reviews the book, "Blood, Sweat, and Fear: Violence at Work in the North American Auto Industry, 1960–80" by Jeremy Milloy.

On the Centennial of the October (Bolshevik) Revolution: A Canticle - Clarke, George Elliott (Labour / Le Travail, 2018)
This poem describes the conditions that lead to the Great October Socialist Revolution that took place in Russia in the year 1917. The Russian Revolution was foundational to the labour and social reforms that took place in Canada in the same era (Winnipeg general strike) and over the course of the next 100 years (healthcare, unions, and credit unions).

The Equity Myth: Racialization and Indigeneity at Canadian Universities - Clément, Dominique (Labour / Le Travail, 2018)
This article reviews the book, "The Equity Myth: Racialization and Indigeneity at Canadian Universities" by Frances Henry, et al.

Bodies and Borders: Migrant Women Farmworkers and the Struggle for Sexual and Reproductive Justice in British Columbia, Canada - Cohen, Amy; Caxaj, Susana (Alternate Routes: A Journal of Critical Social Research, 2018)
In 2016, nearly 7,000 Mexican men and women arrived in BC under the federally-administered Seasonal Agricultural Worker Program (SAWP). While all farmworkers face similar workplace hazards, women farmworkers face unique barriers to their reproductive health and wellbeing such as intense surveillance, sexual harassment, and unwanted pregnancies. The reproductive health of women in the SAWP is under-researched. Even less is known about women’s experiences in the interior of British Columbia. Based on insights gained in the field and through community-based research and advocacy efforts, this paper outlines what is currently known about women SAWP workers’ struggles to attain full reproductive justice. We discuss the unique factors that affect the reproductive health and sexual experiences of SAWP workers in particular. Ultimately, we argue that women SAWP workers face disproportionate barriers when accessing reproductive healthcare and that their sexual behaviour is heavily controlled through a variety of legal and extra-legal mechanisms. We conclude with a discussion on how migrant women creatively resist restrictions imposed upon them, and we make recommendations aimed at improving the experiences of women SAWP workers attempting to achieve reproductive justice in BC.

After Industrial Citizenship: Adapting to Precarious Employment in the Lanarkshire Coalfield, Scotland, and Sudbury Hardrock Mining, Canada - Condratto, Shelley; Gibbs, Ewan (Labour / Le Travail, 2018)

Performants… et licenciés – Enquête sur la banalisation des licenciements - Côté, Josée (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Performants… et licenciés – Enquête sur la banalisation des licenciements," by Mélanie Guyonvarc’h.

Working the Phones: Control and Resistance in Call Centres - Crowley, Martha (Canadian Journal of Sociology, 2018)
The article reviews the book, "Working the Phones: Control and Resistance in Call Centres," by Jamie Woodcock.

Defying Expectations: The Case of UFCW Local 401 - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "Defying Expectations: The Case of UFCW Local 401," by Jason Foster.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Frontiers of Labor: Comparative Histories of the United States and Australia - Dabscheck, Braham (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "Frontiers of Labor: Comparative Histories of the United States and Australia," edited by Greg Patmore and Shelton Stromquist.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; International comparisons; Labor Unions; Meta-analysis; Social sciences

Hard Labor: The Battle that Birthed the Billion-Dollar NBA - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Hard Labor: The Battle that Birthed the Billion-Dollar NBA," by Sam Smith.

The Great Cowboy Strike: Bullets, Ballots and Class Conflicts in the American West - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "The Great Cowboy Strike: Bullets, Ballots and Class Conflicts in the American West," by Mark A. Lause.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Trajectories of Neoliberal Transformation: European Industrial Relations since the 1970s - Dabscheck, Braham (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Trajectories of Neoliberal Transformation: European Industrial Relations since the 1970s," by Lucio Baccaro and Chris Howell.

Labour Market Attainment of Canadian Women in 1921: Influences of Religious Affiliation, Ethnicity, and Linguistic Proficiency - Dilmaghani, Maryam (Labor History, 2018)
The 1921 Canadian Census is exploited to examine the labour market attainment of Canadian women. Acknowledging the general context of Catholic and Protestant divide and the tensions between francophones and anglophones during the WWI, special attention is paid to the influences of religious affiliation, ethnicity, and linguistic proficiency. Working urban women, overwhelmingly unmarried, are found to earn between 68 and 29% less than their male counterparts, depending on occupation and religio-linguistic group. The gender earnings gap is found to be the largest among francophone Catholics. When the sample is restricted to unmarried urban women, francophone Catholic females are found at a large disadvantage compared with anglophone Catholic and Protestant females. Bilingual Catholic women, mostly of French Canadian ethnicity, were the second lowest earning group in Canada of 1921. Bilingual Protestant women, on the other hand, are found to have had the most favourable labour market outcomes. The cumulative weight of the results indicates that among religious affiliation, ethnicity, and linguistic proficiency, ethnicity had exercised the strongest influence on the labour market attainment of Canadian women at that time.

Les peurs au travail - Dompierre, Johanne (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Les peurs au travail," edited by Alain Max Guénette and Sophie Le Garrec.

La discussion des modèles d’action, une condition pour l’action des comités en santé et en sécurité au travail - Dugué, Bernard; Petit, Johann (Relations industrielles / Industrial Relations, 2018)
Le Comité d’hygiène, de sécurité et des conditions de travail (CHSCT) s’avère, en France, une pièce maitresse des dispositifs de prévention des risques et d’amélioration des conditions de travail dans les entreprises. Bien que son rôle soit de plus en plus reconnu, il a souvent des difficultés à fonctionner et à trouver sa place dans le paysage des relations professionnelles.

The Daunting Enterprise of the Law – Essays in Honour of Harry W. Arthurs - Dumas, P. Martin (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "The Daunting Enterprise of the Law -- Essays in Honour of Harry W. Arthurs," edited by Simon Archer, Daniel Drache, and Peer Zumbansen.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Essays; Labor Unions; Labor law; Law; Political economy

After Prison: Navigating Employment and Reintegration - Dunford, David Tyler (Canadian Journal of Sociology, 2018)
The article reviews the book, "After Prison: Navigating Employment and Reintegration," edited by Rose Ricciardelli and Adrienne M.F. Peters.

Race, Exclusion, and Archival Silences in the Seasonal Migration of Tobacco Workers from the Southern United States to Ontario - Dunsworth, Edward (Canadian Historical Review, 2018)
This article explores the role of race in structuring the movement of seasonal tobacco workers from the Southern United States to Ontario from the 1920s to the 1960s. Over this period, tens of thousands of southern migrant workers of varying skill levels travelled to Ontario to take up jobs in all aspects of tobacco production. Participation in the movement was limited exclusively to white workers until 1966, when it was integrated at the behest of American officials fearful of contravening the 1964 Civil Rights Act. Methodologically, the article follows Michel-Rolph Trouillot and is an exercise in uncovering silences in the archive, as civil servants in both countries and employer representatives in Ontario were extremely hesitant about mentioning the movement’s racial character on record. Beyond methodology, the findings presented here contribute to a deeper understanding of the uneven nature of the “deracialization” of Canada’s immigration policies in the 1960s and to charting more of Canada’s role in the construction and maintenance of transnational systems of white supremacy.

Trajectories of Neoliberal Transformation: European Industrial Relations since the 1970s - Dupuis, Mathieu (Labour / Le Travail, 2018)
This article reviews the book, "Trajectories of Neoliberal Transformation: European Industrial Relations since the 1970s" by Lucio Baccaro and Chris Howell.

“A Sharp Offensive in all Directions:” The Canadian Labour Defense League and the Fight against Section 98, 1931–1936 - Eaton, C. Scott (Labour / Le Travail, 2018)
In 1931, eight leaders of the Communist Party of Canada (cpc) were convicted under Section 98 – a federal law that criminalized the advocacy of radical politics – and the party was declared illegal in Canada. The Canadian Labour Defense League (cldl), the party’s ancillary organization responsible for legal matters, conducted an intense campaign directed at securing both the release of the party’s leaders and the repeal of Section 98. This campaign included the distribution of pamphlets, the organization of demonstrations, and even the production of a dramatic play, entitled Eight Men Speak. Canadian state officials, led by Prime Minister R. B. Bennett, responded to the party’s efforts oppressively. Prison guards fired shots into cpc general secretary Tim Buck’s cell in Kingston Penitentiary, and Bennett himself had Eight Men Speak banned from performance in Toronto. Such kneejerk reactions, however, afforded cldl leaders opportunities to conduct meaningful work. This article argues that the cldl skillfully accentuated its own repression, keeping Section 98 relevant to Canada’s voting populace and placing capitalism and the Canadian state on trial in the eyes of the Canadian public.

Technology and the Future of Work: The Impact on Labour Markets and Welfare States - Fast, Travis (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Technology and the Future of Work: The Impact on Labour Markets and Welfare States," by Bent Greve.

The Role of Management and Trade Union Leadership on Dual Commitment: The Mediating Effect of the Workplace Relations Climate - Fortin-Bergeron, Chloe; Doucet, Olivier; Hennebert, Marc-Antonin (Human Resource Management Journal, 2018)
This article examines the effect of transformational and laisser‐faire leadership on the part of local union leaders and immediate supervisors on the dual commitment of unionised workers. Building on the social information processing perspective, it is suggested that these leadership styles are linked to commitment through the workplace relations climate (WRC). Based on a sample of 834 unionised workers, our results suggest that WRC represents an important mechanism explaining the effect of the immediate supervisor's leadership in unionised settings. Results also show that transformational leadership on the part of union representatives is positively linked to union and organisational commitment. This article contributes to the WRC and dual commitment literatures by going beyond structural and institutional explanations and considering relational and actor‐related variables, such as leadership styles.

Unfree Labour? Struggles of Migrant and Immigrant Workers in Canada - Foster, Jason (Labour / Le Travail, 2018)
This article reviews the book, "Unfree Labour? Struggles of Migrant and Immigrant Workers in Canada," edited by Aziz Choudry and Adrian A. Smith.

Les référentiels de compétences comme outils de gestion : concilier les apports déterministes et constructivistes - Foucher, Roland; Rhnima, Aziz (Relations industrielles / Industrial Relations, 2018)
Les démarches relatives aux « compétences », qui marquent la gestion des ressources humaines (GRH) depuis quelques décennies, recourent à des référentiels servant à établir les compétences à maîtriser et déployer. Ces outils de gestion s’inscrivent dans un contexte organisationnel évolutif et interactif suscitant des interrogations, particulièrement sur la façon de les déployer afin qu’ils traduisent les compétences valorisées par les parties concernées et celles effectivement déployées.
Keywords: competence; competence model; competencia; compétence; constructivism; constructivisme; constructivismo; determinism; determinismo; déterminisme; gestion des ressources humaines; gestión de recursos humanos; human resource management; referencial; référentiel

Slavery and Unfree Labour: The Politics of Naming, Framing, and Blaming - Fudge, Judy (Labour / Le Travail, 2018)
The article reviews and comments on the books, "Contemporary Slavery: Popular Rhetoric and Political Practice," edited by Annie Bunting and Joel Quirk, "Modern Slavery: The Margins of Freedom," by Julia O'Connell Davidson, and "The Poverty of Work: Selling Servant, Slave and Temporary Labor on the Free Market," by David Van Arsdale.

Equality on Trial: Gender and Rights in the Modern American Workplace - Fuentes, Kristina (Labour / Le Travail, 2018)
This article reviews the book, "Equality on Trial: Gender and Rights in the Modern American Workplace" by Katherine Turk.

After the International Organization for Migration: recruitment of Guatemalan temporary agricultural workers to Canada - Gabriel, Christina; Macdonald, Laura (Journal of Ethnic and Migration Studies, 2018)
The global agricultural industry is increasingly supported by transnational migrant labour. The experience of this precarious workforce in receiving states has been the focus of intensified scrutiny by policy-makers and academics at the global and national scale. Drawing on field research we examine how the International Organization for Migration was involved in the development of a transnational labour migration corridor from Guatemala to Canada, and how the organisation’s activities are associated with new forms of migration governance. This story, while unique in some ways, illustrates the increased complexity of the international management of migration. For instance, destination states such as Canada continue to play key roles in the management and recruitment of temporary labour migration but other actors have also entered the picture. This development, as this case illustrates, places migrant workers in increasingly vulnerable positions, while states can disclaim responsibility for their plight.

The Second Line of Defense: American Women and World War I - Glassford, Sarah (Labour / Le Travail, 2018)
This article reviews the book, "The Second Line of Defense: American Women and World War I" by Lynn Dumenil.

Writers' Rights: Freelance Journalism in a Digital Age - Gollmitzer, Mirjam (Labour / Le Travail, 2018)
This article reviews the book, "Writers' Rights: Freelance Journalism in a Digital Age" by Nicole Cohen.

Concertation ou négociation? Distinguer les deux afin de faciliter les prises de décisions en contexte de réadaptation au travail - Gouin, Marie-Michelle; Truchon, Manon (Relations Industrielles / Industrial Relations, 2018)
En contexte de réadaptation au travail, l'action concertée (concertation) serait déterminante pour le succes du retour au travail. Or, un débat théorique entoure toujours le concept de concertation ?, qui peut étre rapproché (ou non) de la négociation ?. De plus, aucune étude n'a encore exploré les processus de prises de décisions collectives a partir d'échanges entre les multiples parties prenantes a un programme de réadaptation au travail. Cet article vise a proposer des définitions opérationnelles distinguant la concertation de la négociation, puis a les tester en contexte de réadaptation au travail. D'abord, des définitions de l'action concertée ?, de la concertation et de la négociation sont comparées, afin d'en venir a distinguer ces deux derniers concepts, notamment par la présence de conflit(s) et des relations (de coopération/ collaboration) entre les parties. Les définitions proposées sont, ensuite, testées empiriquement a partir de données issues d'une étude de cas multiples (N=6) qui explore les processus de prises de décisions entre les parties prenantes a un programme de réadaptation au travail. Les données de l'étude montrent l'importance de comprendre la concertation et la négociation comme des types de processus de prises de décisions complexes et dynamiques. L'étude permet aussi de distinguer la concertation et la négociation a l'aide des définitions proposées en contexte de réadaptation au travail. Le recours a ces définitions pourrait engendrer d'importantes retombées, notamment sur le plan des pratiques en réadaptation au travail. Ces définitions pourraient, en effet, permettre de mieux cibler des stratégies a privilégier pour atteindre des décisions favorables au retour durable et en bonne santé des travailleurs en incapacité, selon le type de prise de décisions anticipé. Ceci dit, d'autres études devront venir approfondir la connaissance des processus de prises de décisions collectives (incluant la concertation et la négociation) en contexte de réadaptation au travail, ainsi que leurs liens possibles avec le succes ou l'échec du retour au travail.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Case studies; Collective action; Collectives; Cooperation; Decision making; Definitions; Disability studies; Disabled workers; Handicapped; Interest groups; Intervention; Labor Unions; Negotiation; Negotiations; Operational definitions; Rehabilitation; Return to work programs; Stakeholders; Studies; Success; Work

Agir ensemble. Penser la démocratie syndicale - Grenier, Jean-Noël (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "Agir ensemble. Penser la démocratie sydicale," by Christian Nadeau.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions

Antécédents et efficacité des stratégies de médiation de conflits : le cas des présidents de Commissions mixtes paritaires en France - Grima, François; Brunel, Olivier; Georgescu, Irène; Taphanel, Ludovic (Relations Industrielles / Industrial Relations, 2018)
Le but de cet article est de comprendre la dynamique de mediation en associant ses antecedents, ses differentes manifestations et un resultat : l'accord. Théoriquement, en proposant une approche synthétique qui integre des elements contextuels, comme la presence de tiers ou les caracteristiques des mediateurs, cette recherche realise une contribution academique importante, d'autant que ces elements sont demeures ignores par la litterature. Empiriquement, le choix du contexte français est porteur d'enseignements manageriaux importants. Lorsque le nouveau gouvernement redefinit les fondements du droit du travail en donnant un nouveau rôle a la branche professionnelle, mieux comprendre comment l'action d'un mediateur valorise l'emergence d'un accord nous apparaît fructueux pour tous les partenaires. De meme, ce travail permet de valoriser la complexity du rôle tenu par le mediateur pour l'obtention d'un accord.
Keywords: Agreement; Bias; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Commissions; Ethnocentrism; Interest groups; Intervention; Labor Unions; Mediation; Mediators; Presidents; Quantitative methods; Regulation; Research; Social dynamics; Studies

Mistreatment in Organizations - Haines, Victor Y. (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "Mistreatment in Organizations," edited by Pamela Perrewé, Jonathon Halbesleben, and Christopher Rosen.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Occupational health; Occupational stress

The Rise and Fall of Corporate Social Responsibility - Haiven, Larry (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "The Rise and Fall of Corporate Social Responsibility," by Douglas M. Eichar.

Les organisations en soutien aux démarches de (ré)insertion socioprofessionnelle des personnes en situation d’itinérance : de nouveaux acteurs en relations industrielles au Québec? - Hallée, Yves; Plamondon, Gabrielle (Relations industrielles / Industrial Relations, 2018)
Cet article s’intéresse aux organisations de la société civile (OSC) spécialisées dans le soutien aux démarches de (ré)insertion socioprofessionnelle des personnes en situation d’itinérance (PSI) et aux nouveaux acteurs dans le système de relations industrielles québécois. À partir d’une étude de cas réalisée dans l’Arrondissement Ville-Marie de Montréal, nous avons utilisé les dimensions développées par Bellemare (2000) pour rendre opérationnel le concept d’acteur, les travaux de Heery et al. (2012) sur les OSC britanniques, ainsi que les résultats issus de nos recherches dans cet arrondissement, pour déterminer si les OSC impliquées dans la (ré)insertion socioprofessionnelle des PSI peuvent être considérées comme de nouveaux acteurs en relations industrielles (RI). Selon les dimensions de l’analyse, il apparaît que nous pouvons considérer les OSC qui sont engagées dans des expériences de (ré)insertion socioprofessionnelle des PSI comme de nouveaux acteurs en RI. En effet, en termes d’implication aux divers niveaux d’analyse des RI, elles interviennent de façon ponctuelle sur les lieux de travail, mais de façon beaucoup plus continue sur les plans organisationnel et institutionnel. Au niveau organisationnel, mentionnons que les OSC sont en lien avec des entreprises par le biais d’un réseau entretenu avec une OSC qui agit à titre d’intermédiaire afin de permettre le déploiement des programmes d’employabilité. Il s’agit d’un mode de fonctionnement en réseau où nous retrouvons de nombreux échanges interorganisationnels permettant d’assurer un continuum de services dans le but de soutenir les individus dans leur trajectoire de retour au travail et de faciliter les transitions des PSI en entreprises. En ce qui a trait au degré de continuité de l’implication des OSC dans le système de RI, nos résultats diffèrent de ceux de Heery et al. (2012). Nous avons, en effet, constaté une implication soutenue dans les programmes d’employabilité et de pré-employabilité, alors que ces auteurs parlent plutôt d’implication sporadique ou discontinue. Nos résultats montrent, également, des changements au niveau des règles liées aux conditions de travail et dans l’organisation de l’entreprise par la mutualisation de certaines pratiques de GRH, que nous assimilons à une influence des OSC sur le niveau organisationnel. De plus, ces dernières contribuent indirectement à influencer l’environnement social des entreprises grâce à l’action concertée entre OSC et entreprises dans le but d’apporter une solution au problème de concentration de l’itinérance dans le territoire du centre-ville montréalais.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Pour une approche renouvelée de la gestion des ressources humaines (GRH) = A renewed approach to human resource management (HRM) - Hallée, Yves; Taskin, Laurent; Vincent, Steve (Relations industrielles / Industrial Relations, 2018)
Editorial introduction to the three articles in the issue that call for a renewed approach to human resource management (HRM). Includes bibliography.

Syndicats et responsabilité sociétale de l’entreprise : analyse longitudinale des stratégies des Confédérations françaises - Havard, Christelle; Sobczak, André (Relations industrielles / Industrial Relations, 2018)
Au cours des vingt dernières années, la responsabilité sociétale de l’entreprise (RSE) est devenue une préoccupation majeure du débat public et de la recherche en sciences sociales. La multiplication des démarches RSE a nécessairement un impact sur les organisations syndicales qui sont amenés à s’adapter et à réagir ou qui peuvent se saisir des opportunités offertes par la RSE. L’objectif de cet article est d’apporter un éclairage sur la manière dont les stratégies des centrales syndicales en matière de RSE se construisent.
Keywords: France; Francia; corporate social responsibility; estrategia como práctica; responsabilidad social de empresa; responsabilité sociétale de l’entreprise; sindicato; strategy as practice; stratégie comme pratique; syndicat; union

Firmes multinationales et droits syndicaux : la contribution des alliances syndicales internationales à l’effectivité des Accords-cadres internationaux - Hennebert, Marc-Antonin; Lévesque, Christian; Murray, Gregor; Bourque, Reynald (Relations industrielles / Industrial Relations, 2018)
Cet article s’intéresse à la contribution des alliances syndicales internationales (ASI) à l’effectivité des Accords-cadres internationaux (ACI), notamment à leur capacité à favoriser le processus de syndicalisation et de négociation de conventions collectives dans des pays où la législation nationale peine à assurer le respect de ces droits fondamentaux. Le contenu de ces accords, généralement le fruit d’une entente bilatérale entre la direction d’une multinationale et celle d’une Fédération syndicale internationale, repose habituellement sur certaines conventions de l’OIT dont celles relatives au droit d’association et à la liberté de recourir à la négociation collective.
Keywords: Accord-cadre international; Acuerdo marco internacional; alianzas sindicales internacionales; alliances syndicales internationales; corporate social responsibility; firmas multinacionales; firmes multinationales; international framework agreement; international union alliances; multinational companies; responsabilidad social de empresas; responsabilité sociale des entreprises

The Mexican Heartland: How Communities Shaped Capitalism, a Nation and World History, 1500-2000 - Herrmann, Julián Durazo (Labour / Le Travail, 2018)
The article reviews the book, "The Mexican Heartland: How Communities Shaped Capitalism, a Nation and World History, 1500-2000," by John Tutino.1

Does Employment in Precarious Work Lead to Wage Disparities For Canadian Immigrants? - Hira-Friesen, Parvinder (Canadian Ethnic Studies, 2018)
Using data from the Canadian Labour Force Survey for March of 2006 to 2012, this paper examines how employment in precarious jobs may lead to lower earnings among Canadian newcomers. Results suggest that recent immigrants are struggling financially due to wage disparities created by precarious employment. Both males and females experience an initial earnings disadvantage which is further exacerbated by being employed in involuntary part-time work, temporary work and multiple jobs.

Fiery Joe: The Maverick Who Lit Up the West - Hoffman, George (Labour / Le Travail, 2018)
This article reviews the book, "Fiery Joe: The Maverick Who Lit Up the West" by Kathleen Carlisle.

How the Workers Became Muslims: Immigration, Culture and Hegemonic Transformation in Europe - Hopkins, Carmen Teeple (Labour / Le Travail, 2018)
This article reviews the book, "How the Workers Became Muslims: Immigration, Culture and Hegemonic Transformation in Europe" by Ferruh Yilmaz.

When Prisoners Had a Union: The Canadian Food and Allied Workers Union Local 240 - House, Jordan (Labour / Le Travail, 2018)
Most Canadian prisoners work, yet very little attention has been paid to them as workers by either labour scholars or unions. However, in 1977 the Canadian Food and Allied Workers union (CFAW) organized both incarcerated and non-incarcerated meat cutters into the country's first and only legally recognized union representing primarily prisoners, CFAW Local 240. The union drive came in response to the Ontario government's push to increase prisoners' participation in the workforce, including the introduction of a number of "outside managed industrial programs", which involved private firms operating within provincial correctional facilities. These privately managed industries rekindled some older debates around the potential for prison labour to undermine the wages of free labour, but in the case of the experimental abattoir program at Guelph, they also resulted in something new: unionized prisoners. The union not only made important gains for the workers, but also made modest gains for prisoners' rights. While CFAW Local 240 would eventually be merged into subsequent unions, it continues to serve as a model for working prisoners and represents a rare moment in Canadian history - one where a union organized prison labour instead of opposing it.

Frank Little and the IWW: The Blood That Stained an American Family - Johnson, Jeffrey A. (Labour / Le Travail, 2018)
The article reviews the book, "Frank Little and the IWW: The Blood That Stained an American Family," by Jane Little Botkin.

Neoliberal Capitalism and Precarious Work: Ethnographies of Accommodation and Resistance - Kalleberg, Arne L. (Labour / Le Travail, 2018)
This article reviews the book, "Neoliberal Capitalism and Precarious Work: Ethnographies of Accommodation and Resistance" by Rob Lambert and Andrew Herod.

Le stress au travail, un enjeu de santé - Kamoun, Salima (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "Le stress au travail, un enjeu de santé," by Patrick Légeron.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Emerging Industrial Relations of China - Kaufman, Bruce E. (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "The Emerging Industrial Relations of China," edited by William Brown and Chang Kai.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Evaluating the State of the Employment Relationship: A Balanced Scorecard Approach Built on Mackenzie King’s Model of an Industrial Relations System - Kaufman, Bruce; Barry, Michael; Gomez, Rafael; Wilkinson, Adrian (Relations industrielles / Industrial Relations, 2018)
The industrial relations (IR) field in Canada and the United States (US) emerged in the late 1910s-early 1920s and is thus on the cusp of its 100th anniversary. The impetus for the creation of the IR field was growing public alarm in both countries over the escalating level of conflict, violence, and class polarization in employer-employee relations. The two countries established federal-level government investigative committees, the Royal Commission on Industrial Relations (1919) in Canada and the Commission on Industrial Relations (1911-1915) in the US, to travel cross-country, gather evidence, and report their findings and overall evaluation. To commemorate the IR field’s centenary, this paper conducts the same type of cross-national ER evaluation, but with modern methods. First, this exercise requires a formal evaluation instrument, like a physical exam worksheet. Adopted is a modified version of a balanced scorecard. Second, the scorecard’s framework and questions should be theoretically informed. The framework used is a modified version of the diagrammatic model of an IR system presented by Mackenzie King in Industry and Humanity (1918). The third step is to fill in the scorecard with data from individual workplaces, which are obtained for the US from a new nationally-representative survey of 2000+ workplaces, the State of Workplace Employment Relations Survey (SWERS). The fourth step is to aggregate all the diagnostic measures to obtain a summary numerical estimate for each of the companies of its state of ER performance and health. Based on a 1-7 (7 = highest) scale, then converted to F to A grades, we find that the average ER grade given by managers is B+ and by employees C+. The company scores are graphed in a frequency distribution that visually represents, for the first time in the literature, the lowest-to-highest pattern of employment relations performance and health across the US.
Keywords: IR climate; IR systems; Mackenzie King; balanced scorecard; clima de relaciones industriales; climat des RI; industrial relations (IR) theory; matriz de control equilibrado; sistemas de RI; système d’évaluation équilibré; systèmes de RI; teoría de relaciones industriales (RI); théorie des relations industrielles (RI)

History from the Bottom Up and the Inside Out: Ethnicity, Race, and Identity in Working-Class History - Kealey, Gregory S. (Labour / Le Travail, 2018)
This article reviews the book, "History from the Bottom Up and the Inside Out: Ethnicity, Race, and Identity in Working-Class History" by James R. Barrett.

Learning Bad Habits Across Generations: How Negative Imprints Affect Human Resource Management in the Family Firm - Kidwell, Roland E.; Eddleston, Kimberly A.; Kellermanns, Franz W. (Human Resource Management Review, 2018)
Organizational learning can be a key shared value that perpetuates the family's and the family firm's culture across generations. Imprinting theory helps to explain the impact that lessons learned and transmitted can have on the development of human resources in the family firm. However, the results of imprinting may not necessarily be positive, particularly when imprinting manifests itself in negative processes and expectations. Whereas imprinting and organizational learning are often associated with a “positive halo effect,” they have the potential to result in negative behaviors and deleterious firm-level outcomes. Employing imprinting theory as a framework, we highlight the potential dark side of imprinting within the family firm context and how it can damage human resource efforts and threaten company performance and firm survival. Finally, we suggest how bad habits may be broken and replaced with more effective routines so as to ensure the family firm's continuity and success.

Shaping Graphic History: Primary Sources and Closure in Showdown! Making Modern Unions - Kristofferson, Rob; Orpana, Simon (Labour / Le Travail, 2018)
This research note examines the authors’ graphic history Showdown! Making Modern Unions to build on recent scholarship about the pedagogical use of comics by considering the tools and possibilities this medium opens up to professional historians regarding the treatment of primary sources. We suggest that graphic histories enable strategies for using primary sources that actually enhance and popularize the ways historians can effectively use evidence, particularly in terms of building the critical consciousness of an expanded base of readers. Employing the comics theory concept of closure, we show graphic history to be uniquely situated to allow historians and readers to become actively engaged with and derive meaning from primary sources in a way not possible in other forms of historical writing. Examples from Showdown! are used to show the depth and breadth of these methodological possibilities.

A Critical Analysis of Canada's Sex Work Legislation: Exploring Gendered and Racialized Consequences - Kunimoto, Erica Mika (Stream: Interdisciplinary Journal of Communication, 2018)
In 2013, the Supreme Court of Canada ruled that three sections of the Criminal Code of Canada pertaining to sex work were unconstitutional. In response to this ruling—otherwise known as the Bedford Decision—the Conservative government introduced the Protection of Communities and Exploited Persons Act (PCEPA) in 2014. In this paper, I ask: to what extent does the Protection of Communities and Exploited Persons Act meet its stated goal of addressing the health and safety of those who “engage in prostitution”? In exploring this question, I first trace the legal terrain leading to the PCEPA’s conception. Following this, I show that the PCEPA has failed to address its stated goals in two central ways. First, by co-opting the progressive framing of the Bedford Decision in a way that obscures the situations of violence it seeks to address, and second, by making the most precarious category of sex work even more dangerous through its implementation. In order to render the actual foundations of the PCEPA visible, I draw upon critical race and feminist theory. Through this analysis, I show how gendered and racialized hierarchies regulate violence along and within the sex work spectrum. Overall, this paper argues that the PCEPA has failed to address the health and safety of “those engaged in prostitution,” and instead, has facilitated racialized patterns of gender violence against vulnerable populations.

Documentaries: Poems - Lakevold, Dale (Labour / Le Travail, 2018)
This artcile reviews "Documentaries: Poems" by Walter Hildebrandt.

On Durban's Docks: Zulu Workers, Rural Households, Global Labor - Lalouvière, Paul la Hausse de (Labour / Le Travail, 2018)
The article reviews the book, "On Durban's Docks: Zulu Workers, Rural Households, Global Labor," by Ralph Callebert.

Aboriginal/Non-Aboriginal Wage Gaps in Canada: Evidence from the 2011 National Household Survey - Lamb, Danielle; Yap, Margaret; Turk, Michael (Relations industrielles / Industrial Relations, 2018)
Using data from the 2011 National Household Survey, the present analysis seeks to provide a recent estimate of aboriginal/non-aboriginal earnings disparities for a sample of employees who work full-time, full-year. Wage gaps are estimated and decomposed at the mean for several aboriginal identity groups as well as those living on- and off-reserves. consistent with previous research, the results of the present analysis find earnings disparities are, in general, larger for aboriginal identity respondents (i.e. those who identify themselves as aboriginal persons), as opposed to those who report having aboriginal ancestry, but who do not identify as aboriginal persons. among aboriginal identity groups living off-reserve (First Nations, Métis and Inuit), First Nations experience the largest earnings inequality, followed by Inuit males and Métis. aboriginal identity respondents living on-reserve experience by far the largest earnings disadvantage of all the groups considered in the analysis. the study concludes by discussing the implications of the findings for future research, with an emphasis on the importance of addressing the potential role of discrimination in labour markets.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Occupational Health and Safety Vulnerability of Recent Immigrants Accessing Settlement Services - Lay, A. Morgan; Kosny, Agnieszka; Aery, Anjana; Flecker, Karl; Smith, Peter M. (Canadian Journal of Public Health = Revue Canadienne De Sante Publique, 2018)
Objective: To compare occupational health and safety (OHS) vulnerability of recent Canadian immigrants and workers born in Canada. Methods: Recent immigrants (n = 195) were recruited at four settlement agencies in Southern Ontario, and non-immigrants in Ontario (n = 1030) were contacted by phone and email by a third-party survey provider. The questionnaire measured OHS vulnerability using a 27-item measure and collected sociodemographic and workplace information. Responses were used to evaluate one overall and three specific (policy and procedure, awareness, and empowerment) measures of OHS vulnerability. Log-binomial models compared the overall and policy and procedure-, awareness- and empowerment-related vulnerability of recent immigrants to non-immigrant workers. Models were adjusted for demographic and workplace characteristics. Results: New immigrants experience statistically elevated levels of overall (adjusted risk ratio [ARR] = 1.60, 95% CI 1.23-2.07) and empowerment-related vulnerability (ARR = 1.54, 95% CI 1.09-2.17). Compared to workers born in Canada, immigrants also report elevated levels of policy and procedure vulnerability (ARR = 1.37, 95% CI 0.98-1.92), although this estimate did not meet traditional criteria for statistical significance. Conclusions: This study uses a novel multi-dimensional measure to identify how differences in workplace context place recent immigrant workers at increased risk of work-related injury or illness. Recent immigrant workers experience increased risk of OHS vulnerability. In particular, this vulnerability results from exposure to hazards in combination with inadequate levels of empowerment to protect themselves in the workplace. Policy-makers, advocates, and employers should implement strategies that not only build workplaces where occupational hazards are minimized but also ensure immigrant workers are empowered to act on their workplace rights and engaged to improve workplace safety.
Keywords: Adult; Canada; Emigrants and Immigrants; Emigrants and immigrants; Female; Humans; Male; Middle Aged; Occupational Health; Occupational health; Power, Psychological; Risk Assessment; Surveys and Questionnaires; Vulnerable Populations; Vulnerable populations; Worker

The Great Labour Unrest: Rank-and-File Movements and Political Change in the Durham Coalfield - Laybourn, Keith (Labour / Le Travail, 2018)
The article reviews the book, "The Great Labour Unrest: Rank-and-File Movements and Political Change in the Durham Coalfield," by Lewis H. Mates.

The Life of Ellen Wilkinson, Socialist, Feminist, Internationalist - Laybourn, Keith (Labour / Le Travail, 2018)
This article reviews the book, "The Life of Ellen Wilkinson, Socialist, Feminist, Internationalist" by Laura Beers.

Beyond “Hero-based” Management: Revisiting HRM Practices for Managing Collective Expertise - Lelebina, Olga; Gand, Sébastien (Relations industrielles / Industrial Relations, 2018)
While expert knowledge is a crucial resource for large science-based companies, management of the specific population of experts remains a sensitive issue for the HRM. In order to recognize and retain these employees, companies traditionally implement a dual ladder—a career management tool that proposes an alternative technical career track to the managerial one, thus allowing recognition of an expert status in the organization. However, multiple studies have demonstrated that the implementation of a dual ladder does not bring the expected results. While previous research has investigated the individual aspirations of experts as possible reasons for their dissatisfaction with this managerial tool, we show the importance of the collective dimension of expertise and claim that the latter is insufficiently supported by HRM practices. Drawing on a case study in a large multinational firm, we explore the consequences of individualized practices on expert work and discuss the role of HRM in dealing with so-called “hero-based” management. The findings show that individualized practices could endanger the learning and innovation capacities of the firm and compromise processes such as decision making and problem solving. It could also jeopardize the continuity of expertise from a long-term perspective as younger generations refuse to align with a “hero-based” culture. Despite such a strategic challenge, HR managers experience difficulties in reinforcing the collective dimension of expertise. This opens up new perspectives for the HRM function that could lead the management of experts towards new horizons by supporting the fragile equilibrium between “agency” and “communion” in expertise processes.

On Labour Repression - Leon, Cedric de (Labour / Le Travail, 2018)
The article reviews and comments on the books, "Against Labor: How U.S. Employers Organized to Defeat Union Activism," edited by Rosemary Feurer and Chad Pearson, and "Political Economy of Labor Repression in the United States," by Andrew Kolin.

"We Are All Fast-Food Workers Now": The Global Uprising against Poverty Wages - Luce, Stephanie (Labour / Le Travail, 2018)
The article reviews the book, "'We Are All Fast-Food Workers Now': The Global Uprising against Poverty Wages," by Annelise Orleck.

How Capitalism Destroyed Itself: Technology Displaced by Financial Innovation - Masters, Marick F. (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "How Capitalism Destroyed Itself: Technology Displaced by Financial Innovation," by William Kingston.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Global Labour Studies - Mastrocola, Christopher (Labour / Le Travail, 2018)
The article reviews the book, "Global Labour Studies," by Marcus Taylor and Sébastian Rioux.

Lean Production, Izzat and Industrial Conflict in the Indian Auto Sector: A Case Study - Mathew, Sagi K.; Burgess, John (Relations Industrielles / Industrial Relations, 2018)
The purpose of this article is to highlight the role that Izzat played in the unfolding industrial disputation that emerged at the Toyota plant in Bangalore between 1999 and 2007. Isolated instances contributed to a build-up of employee and community resentment at what was perceived as an attack on Izzat. Behind the events is the attempt to transpose Japanese “lean production and management systems” into an Indian subsidiary where local industrial and cultural conditions were not suitable for the imposition of such practices from headquarters to a subsidiary. The result of the analysis contributes to the understanding of workplace industrial relations (IR) in India and the centrality of Izzat. Within India, the significance of trade unions; the respect of employees; the importance of family and community; the importance of seniority; and the role of respect and honour are factors that multinationals often fail to understand in the design and implementation of their production and HRM systems. The study contributes to the debate over the transferability of standardized HRM policies and practices. MNEs should play a proactive role in supporting the employees of subsidiaries to adjust to and accommodate new paradigms in workplace industrial relations. The aggressive production and HRM practices at the Toyota plant were not compatible with the norms and cultural institutions of the Indian workforce. One of the key implications of this research is that foreign production, organizational and industrial relations systems and practices cannot be transplanted into host-country environments without the due recognition of key cultural conditions, notably Izzat in India.
Keywords: Automobile industry; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Case studies; Community relations; Escalation; Forces and relations of production; Honor; Labor Unions; Labor disputes; Labor process; Labor relations; Management; Production; Studies

Women's ILO: Transnational Networks, Global Labour Standards and Gender Equity, 1919 to Present - McKillen, Elizabeth (Labour / Le Travail, 2018)
The article reviews the book, "Women's ILO: Transnational Networks, Global Labour Standards and Gender Equity, 1919 to Present," edited by Eileen Boris, Dorothea Hoehtker, and Susan Zimmermann.

La fabrique de l’Homme nouveau. Travailler, consommer et se taire ? - Mercure, Daniel (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "La fabrique de l’Homme nouveau. Travailler, consommer et se taire ?," by Jean-Pierre Durand.

The Great Leveler: Violence and the History of Inequality from the Stone Age to the Twenty-First Century - Milloy, Jeremy (Labour / Le Travail, 2018)
This article reviews the book, "The Great Leveler: Violence and the History of Inequality from the Stone Age to the Twenty-First Century" by Walter Scheidel.

An Exceptional Law: Section 98 and the Emergency State, 1919–1936 - Mitchell, Tom (Labour / Le Travail, 2018)
This article reviews the book, "An Exceptional Law: Section 98 and the Emergency State, 1919–1936" by Dennis G. Molinaro.

Fondaction, un Fonds pleinement engagé dans la finance socialement responsable - Morissette, Lucie (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Fondaction, un Fonds pleinement engagé dans la finance socialement responsable," edited by Benoît Lévesque.

Hommage à Jacques Bélanger (1952-2018) / A Tribute to Jacques Bélanger (1952-2018) - Murray, Gregor; Trudeau, Gilles; Lévesque, Christian (Relations Industrielles / Industrial Relations, 2018)
C’est avec tristesse et désarroi que nous apprenions, le 28 juin 2018, le décès de notre collègue et ami, Jacques Bélanger. Comme bien des lecteurs et des lectrices de la revue RI/IR le savent, Jacques Bélanger fut un professeur titulaire renommé du Département des relations industrielles de l’Université Laval, un contributeur fréquent à RI/IR, et le codirecteur et cofondateur du Centre de recherche interuniversitaire sur la mondialisation et le travail, le CRIMT. Intellectuel brillant, théoricien novateur, pédagogue chevronné, comment, dans un espace si restreint, donner un juste aperçu de ce que Jacques fut et de son immense contribution à la recherche et à l’avancement des connaissances sur le travail humain dans ses multiples déclinaisons ? Jacques Bélanger, chercheur de réputation mondiale, est toujours demeuré profondément attaché à ses origines et à Saint-Vallier de Bellechasse, son village.... / Our reaction to news of the death of our dear colleague and friend, Jacques Bélanger, on 28 June 2018, was one of deep sadness and dismay. As so many RI/IR readers will know, Bélanger was a distinguished Professor in the Industrial Relations Department at Université Laval, a frequent contributor to RI/IR, and the co-director and co-founder of the Interuniversity Research Centre on Globalization and Work, the CRIMT. Bélanger was a brilliant intellectual, innovative theorist and accomplished teacher. In the few words permitted here, we can only provide a glimpse of his multiple contributions to research and the advancement of knowledge across diverse aspects of contemporary work and employment. Despite his international renown, Jacques Bélanger was profoundly attached to his origins and, in particular, to his birthplace and village of origin, Saint-Vallier de Bellechasse.....
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Deaths; Employment; Globalization; Labor Unions; Labor relations; Personal profiles; University professors; Work

Wobblies of the World: A Global History of the IWW - Newkirk, Anthony B. (Labour / Le Travail, 2018)
The article reviews the book, "Wobblies of the World: A Global History of the IWW," edited by Peter Cole, David Struthers, and Kenyon Zimmer.

Travail et subjectivité: perspectives critiques - Ngarsandjé, Guelmbaye (Relations industrielles / Industrial Relations, 2018)
This article reviews the book, "Travail et subjectivité : perspectives critiques," by Daniel Mercure and Marie-Pierre Bourdages-Sylvain.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Propaganda and Persuasion: The Cold War and the Canadian-Soviet Friendship Society - Niergarth, Kirk (Labour / Le Travail, 2018)
This article reviews the book, "Propaganda and Persuasion: The Cold War and the Canadian-Soviet Friendship Society" by Jennifer Anderson.

L’effet du mentorat sur la réussite de carrière : quelles différences entre hommes et femmes ? - Ouerdian, Bach; Gara, Emna; Malek, Adnane; Dali, Najwa (Relations industrielles / Industrial Relations, 2018)
Nombreuses sont les recherches ayant examiné l’impact du mentorat sur la réussite de carrière. Toutefois, davantage d’études sont requises afin d’appréhender cette relation, car force est de constater que la majorité des recherches menées jusque-là ont occulté la bi-dimensionnalité de chacun de ces deux construits. Par ailleurs, vu les spécificités féminines, nous estimons que la compréhension de l’impact du mentorat sur la réussite de carrière serait améliorée par l’intégration du genre. Le but de ce travail est de démontrer que le genre joue un rôle modérateur entre le mentorat reçu — estimé par ses deux fonctions instrumentale et psychosociale — et la réussite de carrière aussi bien objective que subjective. Des analyses en équations structurelles, notamment des analyses multigroupes ont été conduites à partir de données recueillies dans le secteur bancaire tunisien auprès de 237 cadres moyens et supérieurs. Nos analyses montrent que les femmes obtiennent moins de promotions et semblent moins satisfaites de leur carrière. Il ressort aussi que les femmes perçoivent moins de soutien de la part de leur mentor, particulièrement d’ordre psychosocial. Si la présente recherche démontre que pour les hommes, comme pour les femmes, le soutien prodigué par le mentor est associé à la réussite de carrière objective, il n’en est pas de même pour le type du mentorat à l’origine de cette réussite. Ainsi, seule la fonction instrumentale favorise l’avancement des femmes, contrairement aux hommes, dont l’avancement est lié uniquement à la fonction psychosociale du mentorat. Enfin, la présente étude indique l’inexistence d’un lien direct entre les fonctions du mentorat et la réussite subjective, et ce, aussi bien pour les hommes que les femmes. Toutefois, nos résultats permettent de mettre en évidence un effet indirect du mentorat psychosocial sur la réussite subjective des hommes par le biais de leur succès objectif.

Anarchism and Transnational Networks in North and South America - Paola, Pietro Di (Labour / Le Travail, 2018)

Social Movement Unionism as Union-Civil Alliances: A Democratizing Force? The New Zealand Case - Parker, Jane; Alakavuklar, Ozan (Relations industrielles / Industrial Relations, 2018)
This exploratory study examines union-civil alliances in New Zealand (NZ). It focuses on the involvement of NZ’s peak union body, the Council of Trade Unions, in three civil group coalitions around the Living Wage Campaign, Decent Work Agenda and Environmental Agenda. It assesses how the CTU and its affiliates’ coalition involvement are informed by and seek to progress liberal (representative), participatory and/or more radical democratic principles, and what this means for organizational practice; the relations between the coalition parties; workplaces; and beyond. Through case discussions, the study finds that civil alliances involving the CTU and its affiliates do not reflect a core trait of union activity in NZ. Among the union-civil alliances that do exist, there is a prevailing sense of their utility to progress shared interests alongside, and on the union side, a more instrumental aim to encourage union revival. However, the alliances under examination reflect an engagement with various liberal and participatory democratic arrangements at different organizational levels. More radical democratic tendencies emerge in relation to ad hoc elements of activity and the aspirational goals of such coalitions as opposed to their usual processes and institutional configurations. In essence, what emerges is a labour centre and movement which, on the one hand, is in a survivalist mode primarily concerned with economistic matters, and on the other, in a position of relative political and bargaining weakness, reaching out to other civil groups where it can so as to challenge the neo-liberal hegemony. Based on our findings, we conclude that Laclau and Mouffe’s (2001) view of radical democracy holds promise for subsequent coalitions involving the CTU, particularly in the context of NZ workers’ diverse interests and the plurality of other civil groups and social movements’ interests. This view concerns on-going agency, change, organizing and strategy by coalitions to build inclusive (counter-) hegemony, arguing for a politic from below that challenges existing dominant neo-liberal assumptions in work and other spheres of life.
Keywords: New Zealand; Nouvelle-Zélande; Nueva Zelandia; alianza civil; alliance civile; centrales sindicales; centrales syndicales; civil alliance; coalición; coalition; coalition-building; democracia liberal; democracia participativa; démocratie libérale; démocratie participative; liberal democracy; mouvement social; movimiento social; participatory democracy; peak body; pensamiento radical; pensée radicale; radical democracy; sindicalismo; social movement unionism (SMU); syndicalisme; trade unions

Immigrants, Communists, and Solidarity Unionism in Niagara, c.1930–1960 - Patrias, Carmela (Labour / Le Travail, 2018)
Focusing on the Niagara region, this study explains the continued adherence of thousands of Canadian workers to communist-led unions during the Cold War era. It argues that co-operation between communist-led unions and communist-led ethnic clubs and other political and social activists in the pursuit of human rights, social justice, and environmental goals explains why thousands of workers continued to adhere to such unions despite intense red-baiting in the 1940s and 1950s. Reaching out to allies beyond the workplace in solidarity unionism was especially important because of the marginalization of communist-led unions within the Canadian labour movement. The study’s findings reinforce the view that local economic and political conditions played a significant role in shaping communist-led unions in Canada. The study also highlights the contribution of interethnic collaboration among immigrant workers to the development of the Canadian labour movement.

Becoming A Dependent Class: Quoddy Herring Fishermen in the 1920s - Payne, Brian (Labour / Le Travail, 2018)
This article explores the labour history of the Maine–New Brunswick sardine herring fishery. It looks specifically at the impact of the 1920–21 recession on weir fishermen who provided juvenile herring fish for the Maine canneries. The article argues that Maine canneries successfully formed a buyers’ trust, which was a widely accepted form of business integration among government and business leaders during the 1920s, and used that trust to break the independence of weir fishermen. The trust used its power to devalue the market price of herring fish and take control of the supply and production of fish, which forced the fishermen into a dependent class. The article thus sheds light on the impact of recessions and recession recoveries on labourers by illustrating the ill effects of market concentration, which is an economic norm following recessions.

Living at Work and Intra-Worker Sociality Among Migrant Farm Workers in Canada - Perry, J. Adam (Journal of International Migration and Integration, 2018)
This article examines how the dormitory labour system as it is employed in the agricultural streams of Canada's Temporary Foreign Worker Program (TFWP) affects workers' everyday sociality. In the article, I demonstrate how the physical compression of home and work into a singular geographic site shapes workers' identities and everyday relationships. Drawing on findings gathered from interviews with migrant farm workers from Mexico and Guatemala working in Southern Ontario, I explore how the requirement to warehouse temporary foreign workers directly on employer property collides with workers' ability to establish an autonomous and dignified life in Canada. In particular, I demonstrate how the TFWP agricultural dormitory system produces inter-generational dynamics that intensify worker self-discipline and generates gender dynamics that support the development of a hyper-productive transnational workforce.
Keywords: Canada; Dormitories; Migrant workers; Precarious work; Temporary foreign worker program; china; flexibility; labor; migration; ontario; power

Revisiting the Law and Governance of Trafficking, Forced Labor and Modern Slavery - Perry, Mike (Labour / Le Travail, 2018)
The article reviews the book, "Revisiting the Law and Governance of Trafficking, Forced Labor and Modern Slavery," edited by Prabha Kotiswaran.

Vers la fin de la gestion des carrières? La GRH face au rôle croissant des intermédiaires du marché du travail - Pichault, François; Lorquet, Nadège; Orianne, Jean-François (Relations industrielles / Industrial Relations, 2018)
La littérature en GRH a longuement discuté les évolutions intervenues dans le champ des carrières en opposant le modèle classique de la carrière organisationnelle au modèle de la carrière nomade, censé répondre au nouveau contrat psychologique qui lie les travailleurs aux organisations du XXIe siècle. Désormais, il s’agirait pour les gestionnaires RH d’attirer des talents dont ils savent que le passage dans l’organisation sera limité dans le temps. Le développement sans précédent des formes de travail au projet, à mi-chemin entre l’emploi salarié et le statut d’indépendant, semble donner raison à cette conception « moderne » de la carrière. Toutefois, une observation plus fine des évolutions en cours sur le marché du travail montre que les carrières des travailleurs au projet ne sont pas seulement le fruit des initiatives individuelles de travailleurs offrant leurs talents sur le marché. Elles passent souvent par des structures d’intermédiation qui, en offrant diverses formules de sécurisation, deviennent des partenaires incontournables de la gestion des trajectoires professionnelles. À partir d’un travail conceptuel sur la notion d’intermédiaire du marché du travail et sur la base de multiples études de cas contrastées sur le marché du travail belge, notre article montre la diversité des formes que peut prendre ce travail d’intermédiation et dégage deux « types idéaux » reflétant des conceptions opposées de la sécurisation des transitions professionnelles : la première considère les travailleurs au projet comme des « quasi-salariés »; la seconde comme des « quasi-indépendants ». Nous montrons, ensuite, en quoi ce jeu triangulaire conduit à une remise en cause de la gestion des carrières en tant qu’attribut régalien de la fonction RH.

67 Shots: Kent State and the End of American Innocence ; Above the Shots: An Oral History of the Kent State Shootings - Powell, Christopher (Labour / Le Travail, 2018)
The article reviews the books, "67 Shots: Kent State and the End of American Innocence," by Howard Means and "Above the Shots: An Oral History of the Kent State Shootings," by Craig S. Simpson and Gregory S. Wilson.

Framing Work: Unitary, Pluralist and Critical Perspectives in the Twenty-first Century ; Perspectives on Contemporary Professional Work - Quinlan, Michael (Relations industrielles / Industrial Relations, 2018)
The article reviews the books, "Framing Work: Unitary, Pluralist and Critical Perspectives in the Twenty-first Century," by Edmund Heery, and "Perspectives on Contemporary Professional Work," edited by Adrian Wilkinson, Donald Hislop and Christine Coupland.

Protecting Labor Rights in Preferential Trade Agreements: The Role of Trade Unions, Left Governments, and Skilled Labor - Raess, Damian; Dür, Andreas; Sari, Dora (The Review of International Organizations, 2018)
This paper investigates variation in the design of labor provisions in preferential trade agreements (PTAs) by focusing on the power of trade unions, the role of government partisanship, and the relative strength of skilled labor. We expect strong trade unions and left-leaning governments to be associated with more, and more far-reaching labor provisions in PTAs. We also expect the strength of skilled workers relative to the strength of unskilled workers to negatively correlate with the depth of labor provisions in PTAs. In addition, the effect of trade unions should be conditional on both the presence of left government and democracy. We test these hypotheses relying on an original dataset of labor provisions included in 483 PTAs signed between 1990 and 2016. This dataset covers 140 different labor provisions that relate to six overarching dimensions. The quantitative analysis finds support for the expectations concerning the influence of trade unions and the role of a country’s skill profile.
Keywords: Design of international institutions; Human rights; Labor provisions; Non-trade issues; Preferential trade agreements

May Morris: Arts and Crafts Designer - Ramsay, Ellen L. (Labour / Le Travail, 2018)
The article reviews the book, "May Morris: Arts and Crafts Designer," by Rowan Bain, Hanne Faurby, Jenny Lister, Anna Mason, and Jan Marsh.

Inclusive Leadership: Realizing Positive Outcomes through Belongingness and Being Valued for Uniqueness - Randel, Amy E.; Galvin, Benjamin M.; Shore, Lynn M.; Ehrhart, Karen Holcombe; Chung, Beth G.; Dean, Michelle A.; Kedharnath, Uma (Human Resource Management Review, 2018)
We introduce a theoretically-grounded conceptualization of inclusive leadership and present a framework for understanding factors that contribute to and follow from inclusive leadership within work groups. We conceptualize inclusive leadership as a set of positive leader behaviors that facilitate group members perceiving belongingness in the work group while maintaining their uniqueness within the group as they fully contribute to group processes and outcomes. We propose that leader pro-diversity beliefs, humility, and cognitive complexity increase the propensity of inclusive leader behaviors. We identify five categories of inclusive leadership behaviors that facilitate group members' perceptions of inclusion, which in turn lead to member work group identification, psychological empowerment, and behavioral outcomes (creativity, job performance, and reduced turnover) in the pursuit of group goals. This framework provides theoretical grounding for the construct of inclusive leadership while advancing our understanding of how leaders can increase diverse work group effectiveness.

Spying on Canadians: The Royal Canadian Mounted Police Security Service and the Origins of the Long Cold War - Reilly, Frances (Labour / Le Travail, 2018)
The article reviews the book, "Spying on Canadians: The Royal Canadian Mounted Police Security Service and the Origins of the Long Cold War," by Gregory S. Kealey.

Topics a Union President Visited to Mobilize Members - Reshef, Yonatan; Keim, Charles (Relations industrielles / Industrial Relations, 2018)
We analyze four calls to action issued by the British Columbia Teachers’ Federation (BCTF) president, Jim Iker. These appeals sought to mobilize members during the 2013-2014 collective bargaining that pitted the BCTF against the British Columbia government and the direct employer, the British Columbia Public School Employers’ Association. We apply a “theory of rhetoric” developed by Chaim Perelman to locate and analyze the topics the BCTF president used to persuade his members to adhere to his arguments about the merit of collective action. We argue that the president constructed his rhetoric by visiting five topics—urgency, fairness, futility, agency, and integrity. The first three promoted a utilitarian logic for collective action. Iker used them to persuade teachers, and other stakeholders, that collective action was necessary for addressing the problem—the futility of the bargaining process to produce a negotiated fair agreement due to the government’s reluctance to bargain in good faith. The last two topics—agency and integrity—comprised a rhetoric of comfort and reassurance offering an affective logic for acting collectively. At least some union members, as well as other stakeholders, might have felt that teachers are expected to care for their charges in the classroom rather than on the picket line, by withdrawing services they monopolize. Iker used the topics of agency and integrity to remind everyone that defending students, young teachers, the teaching profession, and the education system was commendable, and reassured them that collectively they would not be ignored and nor would they fail. In short, we have pointed out five topics that the president visited to mobilize his members to collective action. They highlight a unique rhetoric that aimed to persuade teachers to become agents of protest. Our case study methodology did not allow us to generalize our findings, which more research is, thus, needed to corroborate.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Becoming Your Own Device: Self-Tracking Challenges in the Workplace - Richardson, Steven; Mackinnon, Debra (Canadian Journal of Sociology, 2018)
Workplaces have long sought to improve employee productivity and performance by monitoring and tracking a variety of indicators. Increasingly, these efforts target the health and wellbeing of the employee – recognizing that a healthy and active worker is a productive one. Influenced by managerial trends in personalized and participatory medicine (Swan 2012), some workplaces have begun to pilot their own programs, utilizing fitness wearables and personal analytics to reduce sedentary lifestyles. These programs typically take the form of gamified self-tracking challenges combining cooperation, competition, and fundraising to incentivize participants to get moving. While seemingly providing new arrows in the bio-political quiver – that is, tools to keep employees disciplined yet active, healthy yet profitable (Lupton 2012) – there is also a certain degree of acceptance and participation. Although participants are shaped by self-tracking technologies, “they also, in turn, shape them by their own ideas and practices” (Ruckenstein 2014: 70). In this paper, we argue that instead of viewing self-tracking challenges solely through discourses of power or empowerment, the more pressing question concerns “how our relationship to our tracking activities takes shape within a constellation of habits, cultural norms, material conditions, ideological constraints” (Van Den Eede 2015: 157). We confront these tensions through an empiric case study of self-tracking challenges for staff and faculty at two Canadian universities. By cutting through the hype, this paper uncovers how self-trackers are becoming (and not just left to) their own devices.
Keywords: Organizational studies

Réflexions sur les mutations de la négociation collective - Rioux, Claude (Relations industrielles / Industrial Relations, 2018)
Mon allocution s’inspire de mon expérience et traite de ma réflexion sur la négociation collective, que j’ai longuement fréquentée et pratiquée à la Confédération des syndicats nationaux (CSN) en tant que négociateur syndical dans le secteur manufacturier au Québec et, par la suite, à titre de formateur et collaborateur auprès du Bureau international du Travail (BIT). Je ferai ressortir, à l’aide d’exemples que j’ai vécus, la nature et l’impact des mutations qui ont eu cours quant au rôle régulateur de la négociation collective, ainsi que sur les capacités délibérative et d’adaptation des syndicats. Je traiterai de ce sujet en trois temps. --Introduction

Unions and the City: Negotiating Urban Change - Rose, Joseph B. (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Unions and the City: Negotiating Urban Change," edited by Ian Thomas MacDonald.

Labor Under Fire: A History of the AFL-CIO since 1979 - Rosenfeld, Sam (Labour / Le Travail, 2018)
This article reviews the book, "Labor Under Fire: A History of the AFL-CIO since 1979" by Timothy J. Minchin.

“Caterpillar Hates Unions More Than It Loves Profits”: The Electro-Motive Closure and the Dilemmas of Union Strategy - Ross, Stephanie; Russell, Jason (Labour / Le Travail, 2018)
The February 2012 closure of London, Ontario’s Electro-Motive Diesel by the notoriously anti-union US multinational Caterpillar symbolizes the deep challenges faced by private sector unions in globalized industries. This closure was the final blow in Caterpillar’s negotiations with Canadian Auto Workers Local 27. This article explores the implications of changes in corporate structure, investment, and labour-relations strategy in manufacturing that have reduced capital’s dependence on production and increased corporate power over workers. Through a detailed case study based on extensive analysis of a range of sources, the authors argue that union strategy must be guided by a more differentiated understanding of corporate structure. While unions can effectively mobilize in response to attacks by anti-union employers, union strategy must first be rooted in a careful study of the employer’s structure, strengths and weaknesses, and industry context. Second, unions must develop capacities to intervene at scales beyond the local employment relationship and community. Third, unions must consider more carefully the nature of the various forms of power they seek to deploy and how these forms of power can amplify each other. Even the most effective campaigns will fail to muster leverage over an employer or industry if they neglect developing these forms of knowledge and capacity.

Brokering Servitude: Migration and the Politics of Domestic Labor during the Long Nineteenth Century - Rothera, Evan C. (Relations Industrielles / Industrial Relations, 2018)
The article reviews the book, "Brokering Servitude: Migration and the Politics of Domestic Labor during the Long Nineteenth Century," by Andrew Urban.
Keywords: 19th century; Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Domestic politics; Domestic service; Domestics; Housework; Labor Unions; Labor migration; Middle class; Migration; Politics

Contemporary Slavery: Popular Rhetoric and Political Practice by Christo Aivalis - Savage, Larry (Labour / Le Travail, 2018)
The article reviews the book, "Contemporary Slavery: Popular Rhetoric and Political Practice," by Christo Aivalis.

Socialism & Universal Basic Income - Sculos, Bryant (Class, Race and Corporate Power, 2018)
The idea of universal basic income (UBI) has taken on new life as people experience greater inequality and greater exploitation than ever before—combined with the recurrence of the historically-cyclical fear of mass unemployment driven by rapid advancements in automation technologies. But the idea of providing every person with a certain amount of money, regardless of their socioeconomic status or (in)ability to or (dis)interest in working, is far from universally-accepted by socialists. This essay offers replies to three common socialist criticisms of various basic income proposals, in an effort to defend the radical potential of UBI; a potential that is consonant with the fundamental goal of the socialist project—achieving a democratic, non-exploitative world beyond capitalism.

Inclusive Workplaces: A Review and Model - Shore, Lynn M.; Cleveland, Jeanette N.; Sanchez, Diana (Human Resource Management Review, 2018)
Organizations continue to be challenged and enriched by the diversity of their workforces. Scholars are increasingly focusing on inclusion to enhance work environments by offering support for a diverse workforce. This article reviews and synthesizes the inclusion literature and provides a model of inclusion that integrates existing literature to offer greater clarity, as well as suggestions for moving the literature forward. We review the inclusion literature consisting of the various foci (work group, organization, leader, organizational practices, and climate) and associated definitions and how it has developed. We then describe themes in the inclusion literature and propose a model of inclusion. Finally, we end by discussing theoretical and practical implications.

Unions and the City: Negotiating Urban Change - Siemiatycki, Myer (Labour / Le Travail, 2018)
The article reviews the book, "Unions and the City: Negotiating Urban Change," edited by Ian Thomas MacDonald.

Empty Promises: Why Workplace Pension Law Doesn't Deliver Pensions - Skerrett, Kevin (Labour / Le Travail, 2018)
This article reviews the book, "Empty Promises: Why Workplace Pension Law Doesn't Deliver Pensions" by Elizabeth Shilton.

The First Canadian Bank Strike: Labour Relations and White-Collar Union Organizing during the Second World War - Smith, Julia Maureen (Canadian Historical Review, 2018)
When members of the Office and Professional Workers Organizing Committee (opwoc), employed by the Banque Canadienne Nationale (bcn), set up picket lines at branches in Montreal on 30 April 1942, they began the first strike in the Canadian banking industry. This article analyzes the four-week strike, and the organizing drive that preceded it, as a way of exploring how changes in the relationship between labour, capital, and the state during the Second World War helped or hindered unionization in unorganized industries - areas with limited or non-existent levels of union representation and often predominantly female and racialized workforces. By examining this failed white-collar strike in relation to the substantial increase in labour organizing that occurred in the 1940s and the concomitant changes to the labour relations system, we can consider the effect that these changes had for different types of workers. A closer look at the first Canadian bank strike shows that the changes made to the labour relations system in this period made little difference for the men and women who joined opwoc: the state continued to hamper their organizing effgorts, and the banks continued to oppose and work to thwart unionization. Half-hearted support from labour leaders compounded the problem. Ultimately, the bank's anti-union behaviour, the regional war labour board's drawn-out and disappointing decision on bcn employees' application for increased compensation, and labour leaders' willingness to accept the board's decision undermined the strike and hindered bank workers' efforts to unionize in the early 1940s.

Hesitant Comrades: The Irish Revolution and the British Labour Movement - Smylie, Patrick (Labour / Le Travail, 2018)
This article reviews the book, "Hesitant Comrades: The Irish Revolution and the British Labour Movement" by Geoffrey Bell.

Staying Afloat in the Typing Pool: P.K. Page, Poetry, and the Modern Office - Stacey, Robert (Journal of Canadian Studies, 2018)
In the first few years of the 1940s, poet P.K. Page was employed as a filing clerk for Allied War Supplies, a Montreal-based war firm tasked with producing and distributing materials needed for Canada's war effort. During this time, Page joined the editorial committee of Preview, a socialist poetry magazine to which she contributed a number of poems about office work, workers, and managerial culture. This essay reads that remarkable set of poems through a double lens: it first explores their documentary and diagnostic value as an insider's view of the office during what Graham S. Lowe calls the "administrative revolution"; it then shows how the socialist "work" of these poems is constrained by an aesthetic philosophy that defines the poet and poetry in opposition to labourers and labour-a stance that introduces a number of contradictions that account for the poems' strangely ambivalent and patronizing tone.

Refinery Town: Big Oil, Big Money, and the Remaking of an American City - Stanford-McIntyre, Sarah (Labour / Le Travail, 2018)
The article reviews the book, "Refinery Town: Big Oil, Big Money, and the Remaking of an American City," by Steve Early.

The Contradictions of Pension Fund Capitalism - Stevens, Andrew (Labour / Le Travail, 2018)
The article reviews the book, "The Contradictions of Pension Fund Capitalism," edited by Kevin Skerrett, Johanna Weststar, Simon Archer, and Chris Roberts.

Globalization and Labour in the Twenty-First Century - Stevis, Dimitris (Labour / Le Travail, 2018)
The article reviews the book, "Globalization and Labour in the Twenty-First Century," by Verity Burgmann.

Equal Education, Unequal Jobs: College and University Students with Disabilities - Stewart, Jennifer M.; Schwartz, Saul (Relations industrielles / Industrial Relations, 2018)
Are students with a permanent disability more likely to drop out of post-secondary education than students without a permanent disability? Once they are out of postsecondary education, do their experiences in the labour market differ? Answers to these questions are necessary to evaluate current policies and to develop new policies. This paper addresses these two questions using a unique data set that combines administrative records from the Canada Student Loans Program with survey responses. Our measure of permanent disability is an objective one that requires a physician’s diagnosis. The survey data supply information on the students’ education and labour market status. Simple descriptive statistics suggest that, compared to students without a permanent disability, students with a permanent disability are equally likely to drop out of postsecondary education, but less likely to be in the labour force and more likely to be unemployed. We use propensity score matching to address potential selection into the group of students who documented their disability. The results using propensity score matching are consistent with the descriptive statistics. Our story is one of an underpublicized success—the rising number of students with disabilities in postsecondary institutions and their equal likelihood of graduation—and a persistent problem—the continued disadvantage that people with disabilities, even those with the same educational attainment as people without disabilities, face in the labour market.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Labour Arbitration in Canada - Talarico, Andrea (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Labour Arbitration in Canada," by Morton Mitchnick and Brian Etherington.

Conflits et résistances au travail - Thuderoz, Christian (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Conflits et résistances au travail," by Yvan Sainsaulieu.

Managing Performance through Training and Development - Traoré, Ahmed A. (Relations industrielles / Industrial Relations, 2018)
The article reviews the book, "Managing Performance through Training and Development," 7th ed., by Alan M. Saks and Robert R. Haccoun.

La grève générale des charpentiers-menuisiers de Montréal, 1833-1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le Travail, 2018)
L’histoire est bien connue. En 1833, peu avant que ne débute la saison de la construction, les compagnons charpentiers-menuisiers de Montréal annoncent qu’ils ne travailleront plus au-delà de dix heures par jour, faute de quoi ils recourront à la grève. À la suite d’une victoire partielle auprès des employeurs, le mouvement reprend de plus belle en 1834 et s’étend même aux maçons, aux cordonniers, aux tailleurs et aux boulangers de Montréal. Une alliance de plusieurs maîtres fera toutefois échouer ce mouvement pour la journée de dix heures, dès le mois de mai 1834. Contrairement à ce que prétendait jadis Catherine Vance dans un article de la revue The Marxist Quarterly, rédigé en 1962, nous croyons que l’enjeu de la grève des charpentiers-menuisiers dépassait la seule réclamation de la journée de dix heures. Une enquête approfondie dans les sources nous révèle que nous avons affaire en fait à une lutte de pouvoir entre une nouvelle oligarchie d’entrepreneurs-architectes et une coalition de compagnons et de petits entrepreneurs artisans qui souhaitaient faire reconnaître leur légitimité, dans un contexte où les traditions et les coutumes mutualistes reliées à la pratique du métier de charpentier-menuisier étaient menacées pour la première fois par l’action souterraine de l’économie marchande. Il ressortira de ce conflit deux visions du monde : une conception républicaine du bien commun et de la justice sociale, et une conception libérale du droit de propriété et de l’autorité.

Une nouvelle rubrique sur les politiques du travail et de l’emploi / A New Column on Labour and Employment Policies - Trudeau, Gilles; Bilodeau, Pier-Luc (Relations industrielles / Industrial Relations, 2018)

BC Teachers’ Federation v British Columbia: The Supreme Court Takes a School Holiday - Tucker, Eric (Relations industrielles / Industrial Relations, 2018)
Constitutional labour rights in Canada now protect workers’ freedom to organize and bargain collectively and to strike. These associational freedoms are especially important for public sector workers, the most frequent targets of legislation limiting their freedoms. However, the Supreme Court of Canada judgments recognizing these rights and freedoms have also introduced important ambiguities about their foundation, scope and level of protection. This brief comment locates these ambiguities in the context of Canada’s political economy and industrial relations regime, which are beset by contradiction and conflict. It then explores the origins and development of the jurisprudential ambiguities in constitutional labour rights through a survey of recent Supreme Court of Canada’s labour rights judgments, including most recently British Columbia Teachers’ Federation and British Columbia (2016).

Unions in Court: Organized Labour and the Charter of Rights and Freedoms - Tucker, Eric (Labour / Le Travail, 2018)
This article reviews the book, "Unions in Court: Organized Labour and the Charter of Rights and Freedoms" by Larry Savage and Charles W. Smith.

Multinational Enterprises and Host Country Development - Turki, Sondes (Relations industrielles / Industrial Relations, 2018)
The articles reviews the book, "Multinational Enterprises and Host Country Development," edited by Holger Görg.

L’obligation de disponibilité du salarié au-delà de son temps et de son lieu de travail : les enseignements de la Cour suprême du Canada dans Association des juristes de justice c Canada (Procureur général) - Vallée, Guylaine (Relations industrielles / Industrial Relations, 2018)
Un employeur peut-il imposer à ses employés des périodes de garde obligatoires pendant lesquelles ils doivent être joignables en tout temps afin de pouvoir se rendre au travail rapidement et être en état d’accomplir leur prestation de travail ? Dans un arrêt rendu en 2017, la Cour suprême du Canada estime qu’une telle politique ne constitue pas un exercice raisonnable des droits de direction de l’employeur, mais qu’elle ne porte pas atteinte au droit à la liberté des employés protégé par la Charte canadienne. La démarche utilisée par la Cour pour apprécier ce qu’est l’exercice raisonnable d’un droit de direction représente la principale retombée de cet arrêt. Toutefois, l’analyse de l’obligation de disponibilité sous l’angle de l’atteinte aux droits fondamentaux des employés reste à faire.

The Raiding of Local 480: A Historic Cold War Struggle for Union Supremacy in a Small Canadian City - Verzuh, Ron (Labour / Le Travail, 2018)
The arduous struggle to form Local 480 of the International Union of Mine, Mill and Smelter Workers (Mine-Mill) at Trail, British Columbia, began in 1938. By 1944 it had been certified as the legal bargaining agent for the 5,000 workers at the Consolidated Mining and Smelting Company of Canada (cm&s). But being certified did not spell the end of its problems. Even as World War II was winding down, local and continental anti-Communists attacked the Communist leaders who had founded the local. Among the most determined of the attackers was the United Steelworkers of America (uswa). As the Cold War began, Local 480 was girding for a two-year battle to protect itself from the raiding uswa. Sanctioned by the Congress of Industrial Organizations (cio) to subsume Mine-Mill across North America, the Steelworkers employed an aggressive anti-Communist strategy. In early 1950, when this account begins, Local 480 was in a fight for its life.

From Balconville to Condoville, but Where Is Co-opville? Neighbourhood Activism in 1980s Pointe-Saint-Charles - Vickers, Simon (Labour / Le Travail, 2018)
Historians of postwar Canada have relegated neighbourhood activism to specific periods of city-wide mobilization. In Montréal, for example, authors who participated in or studied urban social movements describe a rapid decline in activism following the first sovereignty referendum in 1980. This periodization of activism has privileged the experiences of a mostly middle-class left who circulated in activist networks spanning the city and has largely ignored the experiences of working-class people who could not afford to stop organizing in their neighbourhoods. During the 1980s, residents in the Montréal neighbourhood of Pointe-Saint-Charles launched projet St-Charles, a plan to build 500 units of co-operative housing to buttress the deindustrializing area against gentrification. Co-ops were a form of low-income housing that some felt could also serve as the organizational basis for a broader movement of poor and working-class people. Plans did not progress exactly as intended; internal race, gender, class, generational, and linguistic tensions within the neighbourhood complicated attempts by local organizers to build a representational movement, as did the social-spending cutbacks that characterized the neoliberal 1980s. Rather than abandon their principles, projet organizers continued to develop co-op housing, thereby sheltering a social fabric and radical critique in Pointe-Saint-Charles from the violent restructuring of the neoliberal city.

Stitch-by-Stitch: An Unsettling Labour of Re-inscription - Vosters, Helene (Canadian Theatre Review, 2018)
On Canada Day 2017, author Helene Vosters hosted a Stitch-by-Stitch Unsettling Canada 150 sewing circle and picnic. Despite intermittent thundershowers, with umbrellas and soggy red thread in hand, a group of twenty to thirty intrepid stitchers embroidered text from the Truth and Reconciliation Commission of Canada’s (TRC) 94 Calls to Action onto Canadian flags. By the time Canada 150 reached its Canada Day zenith, Vosters asserts, it had already become increasingly apparent that the story of a beneficent Canadian nation committed to equity and multicultural inclusivity that the celebrations sought to engender had been significantly eclipsed in mainstream and social media by critiques of the sesquicentennial’s ahistorical premise and its disregard for the ongoing violent effects of settler-colonialism. Against this backdrop, Vosters weaves reflections of the sewing circle as a labour of reinscription with an inquiry into the value (and pitfalls) of embracing what Stó:lō scholar Dylan Robinson and settler scholar Keavy Martin call everyday “aesthetic actions.”

Refus global. Histoire d'une réception partielle - Warren, Jean-Philippe (Labour / Le Travail, 2018)
The article reviews the book, "Refus global. Histoire d'une réception partielle," by Sophie Dubois.

Expedited Arbitration: A Study of Outcomes and Duration - Webb, Shannon R.; Wagar, Terry H. (Relations industrielles / Industrial Relations, 2018)
In both academic and practitioner communities, there is an increased concern related to the time-consuming nature of the traditional labour arbitration system in Canada. The arbitration process was initially instituted to combat the delays and costs experienced in the courts. This study addresses the gap in the scientific literature by considering these ongoing concerns. Many Canadian jurisdictions offer the parties an opportunity to expedite the arbitration process pursuant to applicable legislation. However, despite the opportunity to accelerate the process, there appears to be a reluctance to use the expedited arbitration system. We performed content analysis on over 550 Canadian expedited and traditional labour arbitration cases. The case sample was limited to termination cases. We studied and compared delay at multiple times during the arbitration process, including the delay to the hearing, delay to the arbitration award, and total delay. Furthermore, we studied the case outcome; specifically, whether the grievance was granted or denied and adopted an ordered analysis to investigate differences in case outcomes. Our results support the perception that there is a difference in the expediency of expedited arbitration cases in comparison with traditional arbitration cases. The results also show that the outcomes of dismissal cases, decided in the expedited system, do not significantly differ from the traditional arbitration system. The findings suggest that there are statutorily available opportunities for the parties to accelerate the arbitration process without compromising the results.

Faculty Associations Confront Accountability Governance in Ontario Universities - Webber, Michelle; Butovsky, Jonah (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
Much literature focusing on the academy is concerned with the spread of neo-liberalism into the university sector. We argue that universities in Canada are operating in an era of “accountability governance,” with ideologies, discourses, and practices centred on quality, accountability, and efficiency. We explore the interplay between accountability governance as a regime of power and the work of faculty associations, especially as they strive to preserve faculty members’ professional autonomy and control over their academic work. Using in-depth qualitative interviews with executive members of several Ontario university faculty associations, we explore themes of neo-liberalization and corporatization of the university, shrinking faculty budgets, program reviews, and strategic mandates. While opportunities for action and resistance for faculty unions arise, particularly at the level of senate, more militancy and radicalism are not favoured by many members, as political action is often seen as “unprofessional.”

The Struggle for Development - Weier, Jonathan (Labour / Le Travail, 2018)
The article reviews the book, "The Struggle for Development," by Benjamin Selwyn.

Knights Across the Atlantic: The Knights of Labor in Britain and Ireland - Weir, Robert (Labour / Le Travail, 2018)
This article reviews the book, "Knights Across the Atlantic: The Knights of Labor in Britain and Ireland" by Steven Parfitt.

A Century of Transnationalism: Immigrants and their Homeland Connections - Weise, Julie M. (Labour / Le Travail, 2018)
The article reviews the book, "A Century of Transnationalism: Immigrants and their Homeland Connections," edited by Nancy L. Green and Roger Waldinger.

Prévenir les risques psychosociaux : une étude des perceptions et des pratiques des employeurs - Weissbrodt, Rafaël; Arial, Marc; Graf, Maggie; Ben Jemia, Tarek; Villaret D’Anna, Christine; Giauque, David (Relations industrielles / Industrial Relations, 2018)
L’article porte sur les pratiques mises en oeuvre pour prévenir les risques psychosociaux (RPS) dans les entreprises. Selon les connaissances scientifiques actuelles, réduire ces risques requiert une approche intégrée qui vise à développer les ressources collectives et individuelles des travailleurs, ainsi qu’à réduire leurs contraintes professionnelles. Toutefois très peu de publications ont porté sur la façon dont les employeurs appréhendent effectivement ces questions. L’objectif de cette étude est de mieux comprendre les pratiques de prévention déclarées par des dirigeants d’entreprises, en relation avec la manière dont ils perçoivent l’exposition de leur personnel aux RPS. Nous avons élaboré un cadre d’analyse exploratoire des relations entre la prévention des RPS, la perception des facteurs de risques par les employeurs et diverses caractéristiques des entreprises. Ce cadre a servi de base à une enquête auprès de 404 établissements. À partir d’analyses factorielles et de régressions multiples, l’étude a fait émerger deux modes de prévention : 1- des mesures de gestion spécifique des RPS axées sur les procédures et la formation et liées principalement au risque d’atteinte à l’intégrité personnelle (harcèlement, agressions, discrimination, confrontation à des événements traumatisants) ; et 2- des mesures d’amélioration générale des conditions de travail (organisation, horaires, équipements et environnement de travail) qui peuvent contribuer à renforcer les ressources, mais que les employeurs ne perçoivent guère comme de la prévention des RPS. Les pratiques sont liées à des variables structurelles, ainsi qu’aux modes de participation et de gestion des risques professionnels dans leur ensemble, davantage qu’à la perception de l’employeur concernant l’exposition aux RPS. Les résultats soulignent deux défis pour les autorités. Le premier consiste à faire adopter par les entreprises une approche plus globale, non centrée sur les phénomènes de harcèlement. Le second réside dans le renforcement de mesures de prévention ayant un impact favorable sur l’activité réelle de travail.

The Significance and Shortcomings of Karl Marx - Wright, Chris (Class, Race and Corporate Power, 2018)
In this essay I explain both why Karl Marx remains an important thinker and why he is in some respects inadequate. I focus on the central issue of 'materialism vs. idealism,' and briefly explore ways in which contemporary intellectuals still haven't assimilated the insights of historical materialism. In the last section of the paper I examine the greatest weakness of Marxism, its theory of proletarian revolution, and propose an alternative conceptualization that both updates the theory for the twenty-first century and is more faithful to historical materialism than Marx's own conception was.

Cuban Revolution in America: Havana and the Making of a United States Left, 1968-1992 - Wright, Cynthia (Labour / Le Travail, 2018)
The article reviews the book, "Cuban Revolution in America: Havana and the Making of a United States Left, 1968-1992," by Teishan A. Latner.

Comment saisir la portée des mobilisations de travailleurs informels et précaires ? Une approche féministe matérialiste appliquée à l'économie solidaire brésilienne - Yerochewski, Carole (Relations Industrielles / Industrial Relations, 2018)
Comment analyser la montée de ces nouveaux mouvements de travailleurs que représentent les mobilisations des travailleurs informels et précaires, oů les femmes tiennent une place importante, y compris en termes de leadership ? Les approches traditionnelles en sociologie et en relations industrielles évoquent une montée des identités sociales par rapport aux identités professionnelles, comme s'il s'agissait de la montée d'intérets spécifiques. Â partir d'une redéfinition ontologique du travail qu'ouvre l'approche féministe matérialiste, cet article propose une autre lecture des objets de conflictualité amenés par les mobilisations de travailleuses et de travailleurs informels. Il s'appuie, pour ce faire, sur une étude de cas effectuée dans l'économie solidaire brésilienne et sur le concept d'identité collective de Melucci. Il explore la façon dont ces nouveaux mouvements de travailleurs définissent les processus d'exploitations et de dominations a combattre et la façon dont ils mettent en pratique leurs visions du changement social. Ľarticle met ainsi en lumiére la portée émancipatrice des transformations de leur rapport au travail et souligne, a l'opposé, les réductionnismes qui animent les stratégies syndicales, en particulier quand elles prétendent défendre les droits des travailleurs en développant des coopératives compétitives. Cette approche, qui reconnaît le caractére situé des connaissances, permet de mieux saisir la portée des mobilisations dans l'économie solidaire et le pourquoi des tensions entre syndicats et travailleurs précaires et informels lors des luttes menées par ces derniers.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Case studies; Cooperatives; Dominance; Exploitation; Females; Feminism; Group identity; Identity; Labor Unions; Labor movements; Labor parties; Labor relations; Leadership; Mobilization; Rapport; Reductionism; Rights; Sex roles; Social change; Social cohesion; Sociology; Solidarity movements; Studies; Workers